Adaptive Modeling to Inform Environmental Management - Katie Irving; Rupert Mathwin; Christopher J. Kotalik; J. Angus Webb; David M. Walters; Siwan Lovett; S. Kyle McKay; Christa L. Torrens; John R. Olson; Ziad A. El Jack (Environmental Management, 2026)

Coastal to deep-marine geomorphic classification: A standardised framework and review of terms to support globally consistent mapping - R. Nanson; R. Arosio; J. Gafeira; M. McNeil; D. Dove; L.R. Bjarnadóttir; M.F.J. Dolan; A. Post; S. Nichol; Z. Huang; J. Guinan; O.M. Bialik; et al. (Earth-Science Reviews, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Toward fully automated urban tree inventory: Integrating mobile lidar and open-source tools - Justinn J. Jones; Sorin C. Popescu; Joshuah S. Perkin; Stephen L. Webb (Urban Forestry & Urban Greening, 2026)

Plasticity in the reproductive biology of Yellowstone cutthroat trout Oncorhynchus virginalis bouvieri in Yellowstone Lake following lake trout Salvelinus namaycush invasion - Michelle A. Briggs; Molly A. H. Webb; Christopher S. Guy; Todd M. Koel (Journal of Fish Biology, 2026)
Yellowstone cutthroat trout Oncorhynchus virginalis bouvieri in Yellowstone Lake are the focus of intensive conservation efforts due to the threat of predation by invasive lake trout Salvelinus namaycush . Suppression gillnetting has reduced the abundance of predatory lake trout, and the Yellowstone cutthroat trout population is recovering. Long‐term monitoring indicates the size structure of the population shifted following lake trout invasion, suggesting that reproductive demographic rates of Yellowstone cutthroat trout may have changed. Length at 50% probability of maturity, as assessed using histological analysis of gonadal tissue, was 479 mm (95% confidence interval [CI] 467–490 mm) for females and 406 mm (95% CI 386–430 mm) for males, compared to 330 mm for males and females historically. Currently, age at 50% probability of maturity is 6.6 for females and 5.4 for males. The rate of skipped spawning was 3% for females and 38% for males. Mean absolute fecundity was 2897 ovarian follicles/individual at present compared to 1141 ovarian follicles/individual before lake trout invasion. Mean relative fecundity was 2157 ovarian follicles/kg. This research illustrates the plasticity in the reproductive strategies of fishes as a result of an invasive species. Understanding the reproductive biology of fish populations is vital for effective fisheries management, and these results are integral to a population model that can be used to develop new conservation benchmarks for Yellowstone cutthroat trout.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Genetic signatures of bufadienolide resistance are poor predictors of cane toad toxin resistance in crocodilians - Alexandra K. Ross; Pierre Ibri; Jonathan K. Webb; Tim S. Jessop; Tim Dempster; Charlotte H. Mills; Tahneal Hawke; Mike Letnic; Stephen Frankenberg (Evolutionary Ecology, 2026)

Evaluating a Tri-Institutional Cancer Research Capacity-Building Program for Early-Stage Investigators - Kathryn S. Maxwell; Lecarde Webb; Desiree Rivers; Ann Smith; Emily Hudson; Beverly Taylor; Shailesh Singh; Honghe Wang; Brian M. Rivers; Timothy Turner; Vivian L. Carter; Windy Dean-Colomb; et al. (Journal of Cancer Education, 2026)
The Comprehensive Partnerships to Advance Cancer Health Equity (CPACHE) initiative of the National Cancer Institute (NCI) supports long-standing collaborations between an under-resourced institution and NCI-designated Cancer Centers to strengthen cancer research workforce and advance cancer research capacity. One of the longest continuously funded CPACHE programs is the Morehouse School of Medicine/Tuskegee University/University of Alabama at Birmingham O’Neal Comprehensive Cancer Center tri-institutional partnership. A central component of this partnership is training future generations of investigators, which is accomplished through the research education programs that are designed to build cancer research skills, enhance mentorship, and support career development for all levels from high school students to Early-Stage Investigators (ESIs). This paper evaluates the longitudinal impact of a year-long program for ESIs and postdoctoral fellows since its inception in 2007. The data were extracted from the Research Education Core administrative records about the scholars and mentors and utilized publicly accessible databases Scopus and PubMed for publications, and the NIH RePORTER for grants. Among 89 program scholars, nearly 95% had at least one publication since their program start date. Of these, 70% had a first author, and 62% had a senior author publication. Approximately 20% of scholars obtained NIH funding as principal investigators through grants, core leadership, and/or supplements. This tri-institutional program successfully attracted investigators committed to cancer research. The outcomes suggest that structured training, intensive mentorship, and cross-institutional collaboration can meaningfully support their academic careers. These findings provide insights for strengthening similar programs to continue to meet the evolving professional needs for the development of ESIs and postdoctoral fellows, particularly at under-resourced institutions.

eDNA2IQI: an eDNA/random forest-based prediction tool that accurately predicts ecological status for regulatory-compliance assessment - A.J. Wyness; T. Stoeck; B.J. Morrissey; I. Berrill; K. Davidson; C. FairBairn; S. MacIntyre; C. Webb; T. Foster; S. Brain; D. Svobodova; C. Clark; et al. (Aquaculture, 2026)

Stochastic modeling of bovine tuberculosis dynamics in white-tailed deer - Brandon J. Simony; Ryan S. Miller; Lindsay M. Beck-Johnson; Samuel M. Smith; Colleen T. Webb (Research in Veterinary Science, 2025)

Persistent urinary metabolic signatures in children with type 1 diabetes - Ernesto S. Nakayasu; Javier E. Flores; Lisa M. Bramer; Jackson L. Chin; Young-Mo Kim; Farooq Syed; Erika M. Zink; Brigitte I. Frohnert; Carmella Evans-Molina; Paul B. Kaplowitz; Fran E. Cogen; Rembert Pieper; et al. (Next Research, 2025)

Implications of flooding events for the green‐lipped mussels ( Perna canaliculus ): an aquatic health perspective - Joanna S. Copedo; Stephen C. Webb; Norman L. C. Ragg; Andrea C. Alfaro (New Zealand Journal of Marine and Freshwater Research, 2025)
Flood events are increasingly impacting coastal infrastructures and marine organisms. Prominent among these organisms, the green‐lipped mussel, Perna canaliculus , is an important marine ecosystem engineer and one of New Zealand’s key aquaculture species. Although relatively robust, the species may have limited capacity to tolerate acute environmental shocks such as exposure to riverine floodwater. As flood events become more frequent, they may present serendipitous opportunities for further research. Thirty days into a temperature and starvation co‐stressor experiment, a storm event resulted in the staff evacuation and eventual flooding of the research facility. Additional samples for histology were opportunistically collected after the flood waters receded, and the survival of the P. canaliculus was monitored for two weeks post‐event. Although no mortalities were observed post‐flood exposure, histological results indicate that the event did cause the mussels to spawn. Tissue conditions, such as haemocytosis of the gill and digestive gland atrophy, also appeared to be correlated with the flood event; however, the impact on P. canaliculus health was considered negligible. This research highlights not only the importance of targeted research in elucidating the impacts of climate‐related hazards on marine species but the importance of opportunistically incorporating these unforeseen events into the research.

Decision-making Dynamics of Pregnant and Lactating Women (PLW) Participating in a Community Health and Nutrition Intervention in Jordan - R. Brown; L. Miller; Y. Ren; I. Moore; A. Alghanmi; r. Safadi; P. Webb; R. Shrestha; S. Ghosh (Journal of the Academy of Nutrition and Dietetics, 2025)

Reduced farming density of New Zealand flat oyster Ostrea chilensis is associated with decreased infection by Bonamia ostreae and other parasites - Zoë Hilton; Anne Rolton; Farhana Muznebin; Stephen C. Webb; Andrew Fidler; Andrew Elliot; Javier Atalah; Andrea C. Alfaro; Kate S. Hutson (Aquaculture, 2025)

Developmental transcriptomes predict adult social behaviours in the socially flexible sweat bee, Lasioglossum baleicum - Kennedy S. Omufwoko; Adam L. Cronin; Thi Thu Ha Nguyen; Andrew E. Webb; Ian M. Traniello; Sarah D. Kocher (Molecular Ecology, 2025)
Natural variation can provide important insights into the genetic and environmental factors that shape social behaviour and its evolution. The sweat bee, Lasioglossum baleicum , is a socially flexible bee capable of producing both solitary and eusocial nests. We demonstrate that within a single nesting aggregation, soil temperatures are a strong predictor of the social structure of nests. Sites with warmer temperatures in the spring have a higher frequency of social nests than cooler sites, perhaps because warmer temperatures provide a longer reproductive window for those nests. To identify the molecular correlates of this behavioural variation, we generated a de novo genome assembly for L. baleicum , and we used transcriptomic profiling to compare adults and developing offspring from eusocial and solitary nests. We find that adult, reproductive females have similar expression profiles regardless of social structure in the nest, but that there are strong differences between reproductive females and workers from social nests. We also find substantial differences in the transcriptomic profiles of stage‐matched pupae from warmer, social‐biased sites compared to cooler, solitary‐biased sites. These transcriptional differences are strongly predictive of adult reproductive state, suggesting that the developmental environment may set the stage for adult behaviours in L. baleicum . Together, our results help to characterize the molecular mechanisms shaping variation in social behaviour and highlight a potential role of environmental tuning during development as a factor shaping adult behaviour and physiology in this socially flexible bee.

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Evolutionary Triggers of Plant Speciation in the Himalaya‐Tibet‐Hengduan Biodiversity Epicentre - Maharaj K. Pandit; Kumar Manish; Sandeep Sen; Kamaljit S. Bawa; Andrew H. Knoll; A. Alexander G. Webb; Peter D. Clift; Fabien L. Condamine; Carina Hoorn (Journal of Biogeography, 2025)
Background Past studies linking geologic and climatic controls on speciation in the Himalaya, Tibet and Hengduan (HTH) regions do not fully capture the mechanisms underlying patterns of plant diversity and endemism in hyperdiverse mountain ecosystems. Aims This study sheds new light on the orogenic and climatic drivers of plant endemism and diversity in the HTH region and unravels the mechanisms behind plant speciation and assembly. Materials & Methods We re‐examine the past findings on geo‐climatic controls on speciation in the HTH. We also analyse new datasets on the elevational patterns of endemic species richness in the HTH regions and correlate these with the hypsometric profiles based on digital elevation models of these regions. Results We discover that the phased evolution of HTH mountain‐building and climate oscillations, and species radiations were not exactly synchronous, but were interspersed with periods of inactivity. We find an inverse yet overlapping relationship between elevation‐area troughs (EATs) of hypsometric profiles and peaks of endemic plant richness in the HTH, indicating that most endemic species occupy the higher elevational belts with the least geographic areas. These elevational belts comprise geographically and biologically isolated habitats. Discussion and Conclusions We infer that orogeny, monsoon and glaciations have shaped the highly dissected HTH landscapes, characterised by high‐relief topography, leading to population isolation, speciation and endemism, albeit with temporal lags. Glacial–interglacial cycles have further promoted isolation, co‐habitation, hybridisation and polyploidy among plant populations, generating and accelerating endemic radiations. Our results provide crucial evidence linking mountain‐building, climatic events and landform development with plant species richness and endemism in the HTH regions and potentially in other mountain ecosystems.

Elucidating divergent growth and climate vulnerability in abalone (Haliotis iris): A multi-year snapshot - Joanna S. Copedo; Stephen C. Webb; Lizenn Delisle; Ben Knight; Norman L.C. Ragg; Olivier Laroche; Leonie Venter; Andrea C. Alfaro (Marine Environmental Research, 2025)

Within-species variation eclipses between-species differences in Pan consolation - Jake S. Brooker; Christine E. Webb; Stephanie Kordon; Frans B.M. de Waal; Zanna Clay (Evolution and Human Behavior, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Dust transport pathways from The Great Basin - Ronald S. Treminio; Nicholas P. Webb; Saroj Dhital; Akasha Faist; Beth Newingham; Colby Brungard; David DuBois; Brandon L. Edwards; Emily Kachergis (Aeolian Research, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

The White Hills Gravel of central Victoria: an anomalous Paleogene very coarse-grained fluvial deposit - C. J. Van Praagh; J. A. Webb; S. Q. White (Australian Journal of Earth Sciences, 2024)

Redox cycling-based signal amplification at alkanethiol modified nanoporous gold interdigitated microelectrodes - Yi Liu; Ajith Mohan Arjun; Sean Webb; Monica Wolfe; Jorge L. Chávez; Nathan S. Swami (Analytica Chimica Acta, 2024)

Born of fire, borne by water – Review of paleo-environmental conditions, floristic assemblages and modes of preservation as evidence of distinct silicification pathways for silcrete floras in Australia - Andrew C. Rozefelds; John Webb; Raymond J. Carpenter; Anita K. Milroy; Robert S. Hill (Gondwana Research, 2024)

Imperfect adaptation by freshwater crocodiles to the invasion of a toxic prey species - Mike Letnic; Tim Dempster; Tim S. Jessop; Jonathan K. Webb (Biological Invasions, 2024)
Novel interactions between invaders and native species that have evolved in their absence may impose strong selective pressures that drive species to extinction or prompt rapid co-evolution and learning. Here, we report on the effects that invasive cane toads, a toxic prey species, have had on freshwater crocodile populations in 7 waterholes of the Victoria River, Australia, before and up to 14 years after toads invaded. We recorded observations of crocodiles attacking toads, dissected dead crocodiles to determine if they had eaten toads and indexed the abundances of cane toads, live crocodiles and dead crocodiles. Following toad-invasion we observed crocodiles attacking cane toads. Dead crocodiles were only observed following the invasion of toads and 62% of the 71 dead crocodiles we dissected had toads in their stomachs. Counts of dead crocodiles showed a humped relationship with time since toad invasion and declined markedly after 3 years post-toad invasion. Live crocodile abundance declined sharply following toad-invasion, but this decline attenuated approximately 4 years post-invasion. The pulse of crocodile mortality and attenuation of the rate of crocodile population decline suggests that crocodiles have evolved or learned to enable co-existence with toads. However, crocodile populations have shown no sign of recovery in the 8–14 years post toad invasion. Our findings highlight that adaptation by native species to the presence of invaders may be imperfect and thus may not necessarily entail numerical recovery of populations to pre-invasion levels, but instead downward shifts to new equilibria due to ongoing interactions with invaders.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Content Validity of the Modified Functional Scale for the Assessment and Rating of Ataxia (f-SARA) Instrument in Spinocerebellar Ataxia - Michele Potashman; Katja Rudell; Ivanna Pavisic; Naomi Suminski; Rinchen Doma; Maggie Heinrich; Linda Abetz-Webb; Melissa Wolfe Beiner; Sheng-Han Kuo; Liana S. Rosenthal; Theresa Zesiwicz; Terry D. Fife; et al. (The Cerebellum, 2024)
The functional Scale for the Assessment and Rating of Ataxia (f-SARA) assesses Gait, Stance, Sitting, and Speech. It was developed as a potentially clinically meaningful measure of spinocerebellar ataxia (SCA) progression for clinical trial use. Here, we evaluated content validity of the f-SARA. Qualitative interviews were conducted among individuals with SCA1 ( n = 1) and SCA3 ( n = 6) and healthcare professionals (HCPs) with SCA expertise (USA, n = 5; Europe, n = 3). Interviews evaluated symptoms and signs of SCA and relevance of f-SARA concepts for SCA. HCP cognitive debriefing was conducted. Interviews were recorded, transcribed, coded, and analyzed by ATLAS.TI software. Individuals with SCA1 and 3 reported 85 symptoms, signs, and impacts of SCA. All indicated difficulties with walking, stance, balance, speech, fatigue, emotions, and work. All individuals with SCA1 and 3 considered Gait, Stance, and Speech relevant f-SARA concepts; 3 considered Sitting relevant (42.9%). All HCPs considered Gait and Speech relevant; 5 (62.5%) indicated Stance was relevant. Sitting was considered a late-stage disease indicator. Most HCPs suggested inclusion of appendicular items would enhance clinical relevance. Cognitive debriefing supported clarity and comprehension of f-SARA. Maintaining current abilities on f-SARA items for 1 year was considered meaningful for most individuals with SCA1 and 3. All HCPs considered meaningful changes as stability in f-SARA score over 1–2 years, 1–2-point change in total f-SARA score, and deviation from natural history. These results support content validity of f-SARA for assessing SCA disease progression in clinical trials.

Marginal snowpacks: The basis for a global definition and existing research needs - J.I. López-Moreno; N. Callow; H. McGowan; R. Webb; A. Schwartz; S. Bilish; J. Revuelto; S. Gascoin; C. Deschamps-Berger; E. Alonso-González (Earth-Science Reviews, 2024)

Damage to tropical forests caused by cyclones is driven by wind speed but mediated by topographical exposure and tree characteristics - Thomas Ibanez; David Bauman; Shin‐ichiro Aiba; Thomas Arsouze; Peter J. Bellingham; Chris Birkinshaw; Philippe Birnbaum; Timothy J. Curran; Saara J. DeWalt; John Dwyer; Thierry Fourcaud; Janet Franklin; et al. (Global Change Biology, 2024)
Each year, an average of 45 tropical cyclones affect coastal areas and potentially impact forests. The proportion of the most intense cyclones has increased over the past four decades and is predicted to continue to do so. Yet, it remains uncertain how topographical exposure and tree characteristics can mediate the damage caused by increasing wind speed. Here, we compiled empirical data on the damage caused by 11 cyclones occurring over the past 40 years, from 74 forest plots representing tropical regions worldwide, encompassing field data for 22,176 trees and 815 species. We reconstructed the wind structure of those tropical cyclones to estimate the maximum sustained wind speed (MSW) and wind direction at the studied plots. Then, we used a causal inference framework combined with Bayesian generalised linear mixed models to understand and quantify the causal effects of MSW, topographical exposure to wind (EXP), tree size (DBH) and species wood density ( ρ ) on the proportion of damaged trees at the community level, and on the probability of snapping or uprooting at the tree level. The probability of snapping or uprooting at the tree level and, hence, the proportion of damaged trees at the community level, increased with increasing MSW, and with increasing EXP accentuating the damaging effects of cyclones, in particular at higher wind speeds. Higher ρ decreased the probability of snapping and to a lesser extent of uprooting. Larger trees tended to have lower probabilities of snapping but increased probabilities of uprooting. Importantly, the effect of ρ decreasing the probabilities of snapping was more marked for smaller than larger trees and was further accentuated at higher MSW. Our work emphasises how local topography, tree size and species wood density together mediate cyclone damage to tropical forests, facilitating better predictions of the impacts of such disturbances in an increasingly windier world.

Can freshwater plants and algae act as an effective feed supplement to reduce methane emissions from ruminant livestock? - Rebecca E. Lester; Ashley Macqueen; Emily K. Armstrong; David T. Dodemaide; Georgia K. Dwyer; Thomas S. Mock; Stephanie Payne; Michael Smith; Michaela Storen; Lawrence Webb (Science of The Total Environment, 2024)

ACPSEM position paper: pre-treatment patient specific plan checks and quality assurance in radiation oncology - Lotte S. Fog; Luke K. Webb; Jeffrey Barber; Matthew Jennings; Sam Towns; Susana Olivera; John Shakeshaft (Physical and Engineering Sciences in Medicine, 2024)

Histopathological investigation of four populations of abalone (Haliotis iris) exhibiting divergent growth performance - Joanna S. Copedo; Stephen C. Webb; Norman L.C. Ragg; Leonie Venter; Andrea C. Alfaro (Journal of Invertebrate Pathology, 2024)

Coyotes eat flies at carrion - David S. Mason; Abby K. Jones; Brandon T. Barton; Mike Proctor; Stephen L. Webb; Marcus A. Lashley (Food Webs, 2023)

Organic sulfur from source to sink in low‐sulfate Lake Superior - Alexandra A. Phillips; Imanol Ulloa; Emily Hyde; Julia Agnich; Lewis Sharpnack; Katherine G. O'Malley; Samuel M. Webb; Kathryn M. Schreiner; Cody S. Sheik; Sergei Katsev; Morgan Reed Raven (Limnology and Oceanography, 2023)
Organic sulfur plays a crucial role in the biogeochemistry of aquatic sediments, especially in low sulfate ( μ M) environments like freshwater lakes and the Earth's early oceans. To better understand organic sulfur cycling in these systems, we followed organic sulfur in the sulfate‐poor ( μ M) iron‐rich (30–80 μ M) sediments of Lake Superior from source to sink. We identified microbial populations with shotgun metagenomic sequencing and characterized geochemical species in porewater and solid phases. In anoxic sediments, we found an active sulfur cycle fueled primarily by oxidized organic sulfur. Sediment incubations indicated a microbial capacity to hydrolyze sulfonates, sulfate esters, and sulfonic acids to sulfate. Gene abundances for dissimilatory sulfate reduction ( dsrAB ) increased with depth and coincided with sulfide maxima. Despite these indicators of sulfide formation, sulfide concentrations remain low (

An agent-based model to quantify energetics, movement and habitat selection of mid-continent mallards in the Mississippi Alluvial Valley - Florian G. Weller; Elisabeth B. Webb; Sean Fogenburg; William S. Beatty; Dylan Kesler; Robert H. Blenk; Kevin M. Ringelman; Matt L. Miller; Céline Arzel; John M. Eadie (Ecological Modelling, 2023)

Comparative analysis of animal lifespan - Nicole C. Riddle; Peggy R. Biga; Anne M. Bronikowski; James R. Walters; Gerald S. Wilkinson; Jingyue Ellie Duan; Anthony Gamble; Erica Larschan; Richard P. Meisel; Ritambhara Singh; Ashley Webb (GeroScience, 2023)
Comparative studies of aging are a promising approach to identifying general properties of and processes leading to aging. While to date, many comparative studies of aging in animals have focused on relatively narrow species groups, methodological innovations now allow for studies that include evolutionary distant species. However, comparative studies of aging across a wide range of species that have distinct life histories introduce additional challenges in experimental design. Here, we discuss these challenges, highlight the most pressing problems that need to be solved, and provide suggestions based on current approaches to successfully carry out comparative aging studies across the animal kingdom.

Histopathological changes in the greenshell mussel, Perna canaliculus, in response to chronic thermal stress - Joanna S. Copedo; Stephen C. Webb; Norman L.C. Ragg; Jessica A. Ericson; Leonie Venter; Alfonso J. Schmidt; Natalí J. Delorme; Andrea C. Alfaro (Journal of Thermal Biology, 2023)

Bioactive (Poly)phenol Concentrations in Plant-based Milk Alternatives in the US Market - A. Kennedy; K. Jiang; E. Grainger; M. Webb; C. Chitchumroonchokchai; K. Riedl; M. Manubolu; S. Clinton (Journal of the Academy of Nutrition and Dietetics, 2023)

Florida-California Cancer Health Equity Center (CaRE2) Community Scientist Research Advocacy Program - B. Hensel; N. Askins; E. Ibarra; C. Aristizabal; I. Guzman; R. Barahona; B. Hazelton-Glenn; J. Lee; Z. Zhang; F. Odedina; D. J. Wilkie; M. C. Stern; et al. (Journal of Cancer Education, 2023)
The Community Scientist Program (CSP), a model connecting researchers with community members, is effective to inform and involve the general population in health-related clinical research. Given the existing cancer disparities among Black/African American and Hispanic/Latino/a populations, more models describing how cancer-related CSPs are designed, implemented, and evaluated are needed. The Florida-California Cancer Research, Education and Engagement (CaRE 2 ) Health Equity Center is a tri-institutional, bicoastal center created to eliminate cancer health disparities among Black/African American and Hispanic/Latino/a populations living in California and in Florida. The CaRE 2 Center created a Community Scientist Research Advocacy (CSRA) training program for community members to become cancer research advocates. The CSRA program is currently a 13-week program conducted 100% virtually with all materials provided in English and Spanish for participants to learn more about prostate, lung, and pancreas cancers, ongoing research at CaRE 2 , and ways to share cancer research throughout their communities. Participants attend didactic lectures on cancer research during weeks 1–5. In week 4, participants join CSRA self-selected groups based on cancer-related topics of interest. Each group presents their cancer-related advocacy project developed during weeks 5–12 at the final session. In this paper, we describe the CaRE 2 Health Equity Center’s CSRA program, share results, and discuss opportunities for improvement in future program evaluation as well as replication of this model in other communities.

Training Community African American and Hispanic/Latino/a Advocates on Prostate Cancer (PCa): a Multicultural and Bicoastal Approach - Carolina Aristizabal; Sandra Suther; Yingwei Yao; Linda S. Behar-Horenstein; Fern Webb; Mariana C. Stern; Lourdes Baezconde-Garbanati (Journal of Cancer Education, 2023)
African American communities are disproportionately impacted by prostate cancer (PCa) compared to other racial/ethnic groups. Whereas the incidence of PCa in Hispanic/Latino men is lower than the incidence in non-Hispanic/Latino White men, Hispanic/Latino men are more likely to be diagnosed with PCa in late stages, and less likely to be knowledgeable about PCa, resulting in significant disparities. We developed, culturally adapted, translated, implemented, and evaluated a PCa Cancer Advocacy Training in African American and Hispanic/Latino/a communities. Culturally and language specific content for African American and Hispanic/Latino/a patients on PCa causes, risk factors, epidemiology, detection, diagnosis, and treatment were delivered through a workshop and simultaneously broadcasted in Spanish in Los Angeles County ( n = 29) and in English in Tallahassee, FL ( n = 9). Pre- and posttest surveys assessed impact. Pre vs post differences were statistically significant in knowledge (5.0 ± 1.6 vs 6.3 ± 1.1) and advocacy intentions (3.9 ± 0.9 vs 4.3 ± 0.8), on correctly identifying warning signs for PCa (50% vs 87%), intent to inform and educate about PCa within the next 3 months (69% vs 95%), to ensure that high-quality research is sensitive to the priorities of patients (63% vs 84%), to help increase patient recruitment, compliance, and retention for clinical trials within the next month (62% vs 84%), intent to engage in PCa patient education within the next 3 months (67% vs 92%), and in engaging in PCa community outreach within the next 3 months (67% vs 94%). There were no significant differences due to race/ethnicity. The Cancer Advocacy Training led to increased knowledge, awareness, and intention to engage in advocacy regarding PCa in the next 3 months. Results suggest that delivering culturally and language specific educational information increases engagement of Hispanic/Latino/a and African American patient/community advocates.

S12-01: Physiologically-Based Kinetic (PBK) Models and Applications In Read-Across - J. Madden; C. Thompson; S. Webb; P. Penson; C. Tan; A. Paini (Toxicology Letters, 2023)

Satellites reveal Earth's seasonally shifting dust emission sources - Adrian Chappell; Nicholas P. Webb; Mark Hennen; Kerstin Schepanski; Philippe Ciais; Yves Balkanski; Charles S. Zender; Ina Tegen; Zhenzhong Zeng; Daniel Tong; Barry Baker; Marie Ekström; et al. (Science of The Total Environment, 2023)

Identification, transformations and mobility of hazardous arsenic-based pigments on 19th century bookbindings in accessible library collections - Marc Vermeulen; Samuel M. Webb; Susan Russick; Alicia C. McGeachy; Karissa Muratore; Marc S. Walton (Journal of Hazardous Materials, 2023)

Blood chemistry and biliverdin differ according to reproduction and tourism in a free-living lizard - Susannah S. French; Erin L. Lewis; Kwanho C. Ki; Zachary E. Cullen; Alison C. Webb; Charles R. Knapp; John B. Iverson; Michael W. Butler (Journal of Comparative Physiology B, 2023)

Spawning Locations of Pallid Sturgeon in the Missouri River Corroborate the Mechanism for Recruitment Failure - Tanner L. Cox; Christopher S. Guy; Luke M. Holmquist; Molly A. H. Webb (Fishes, 2023)
Conservation propagation of pallid sturgeon (Scaphirhynchus albus) upstream of Fort Peck Reservoir, MT, USA, has successfully recruited a new generation of spawning-capable pallid sturgeon where there would otherwise be fewer than 30 remaining wild reproductively mature pallid sturgeon. Successful recovery of pallid sturgeon will now rely on the behavior of pallid sturgeon (e.g., successful spawning in locations that provide adequate drift distance for larvae to recruit). We used location data of pallid sturgeon during four putative spawning seasons to answer the following questions: Where do pallid sturgeon spawn? Are spawning locations related to discharge? Are substrate characteristics at the spawning locations similar to other river reaches? Do spawning-capable females, spawning-capable males, and female pallid sturgeon undergoing mass ovarian follicular atresia use the river similarly? Additionally, we considered if spawning locations are far enough from the river–reservoir transition zone to provide adequate drift distance for larvae to recruit. Spawning-capable pallid sturgeon did explore upstream locations, and four spawning-capable pallid sturgeon were located in the Marias River during the spawning season in 2018 when discharge was at an unprecedented high. Pallid sturgeon exited the Marias River and moved downstream prior to spawning, and when spawning occurred, it was not far enough upstream to prevent larvae from entering the transition zone of Fort Peck Reservoir. Thus, management of discharge and water temperature to mimic 2018 conditions may increase use of the Marias River by pallid sturgeon during the spawning season, which would increase drift distance available to larvae and increase the probability of successful recruitment.

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

Forecasting solar photosynthetic photon flux density under cloud cover effects: novel predictive model using convolutional neural network integrated with long short-term memory network - Ravinesh C. Deo; Richard H. Grant; Ann Webb; Sujan Ghimire; Damien P. Igoe; Nathan J. Downs; Mohanad S. Al-Musaylh; Alfio V. Parisi; Jeffrey Soar (Stochastic Environmental Research and Risk Assessment, 2022)
Forecast models of solar radiation incorporating cloud effects are useful tools to evaluate the impact of stochastic behaviour of cloud movement, real-time integration of photovoltaic energy in power grids, skin cancer and eye disease risk minimisation through solar ultraviolet (UV) index prediction and bio-photosynthetic processes through the modelling of solar photosynthetic photon flux density (PPFD). This research has developed deep learning hybrid model (i.e., CNN-LSTM) to factor in role of cloud effects integrating the merits of convolutional neural networks with long short-term memory networks to forecast near real-time (i.e., 5-min) PPFD in a sub-tropical region Queensland, Australia. The prescribed CLSTM model is trained with real-time sky images that depict stochastic cloud movements captured through a total sky imager (TSI-440) utilising advanced sky image segmentation to reveal cloud chromatic features into their statistical values, and to purposely factor in the cloud variation to optimise the CLSTM model. The model, with its competing algorithms (i.e., CNN, LSTM, deep neural network, extreme learning machine and multivariate adaptive regression spline), are trained with 17 distinct cloud cover inputs considering the chromaticity of red, blue, thin, and opaque cloud statistics, supplemented by solar zenith angle (SZA) to predict short-term PPFD . The models developed with cloud inputs yield accurate results, outperforming the SZA -based models while the best testing performance is recorded by the objective method (i.e., CLSTM) tested over a 7-day measurement period. Specifically, CLSTM yields a testing performance with correlation coefficient r = 0.92, root mean square error RMSE = 210.31 μ mol of photons m −2 s −1 , mean absolute error MAE = 150.24 μ mol of photons m −2 s −1 , including a relative error of RRMSE = 24.92% MAP E = 38.01%, and Nash Sutcliffe’s coefficient E NS = 0.85, and Legate and McCabe’s Index LM = 0.68 using cloud cover in addition to the SZA as an input. The study shows the importance of cloud inclusion in forecasting solar radiation and evaluating the risk with practical implications in monitoring solar energy, greenhouses and high-value agricultural operations affected by stochastic behaviour of clouds. Additional methodological refinements such as retraining the CLSTM model for hourly and seasonal time scales may aid in the promotion of agricultural crop farming and environmental risk evaluation applications such as predicting the solar UV index and direct normal solar irradiance for renewable energy monitoring systems.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Combined reduced expression of two gene families lowers nicotine content to ultra-low levels in cultivated tobacco - Sheri P. Kernodle; Sydney Webb; Tyler M. Steede; Ramsey S. Lewis (Plant Cell Reports, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

TUBB3 Arg262His causes a recognizable syndrome including CFEOM3, facial palsy, joint contractures, and early-onset peripheral neuropathy - Mary C. Whitman; Brenda J. Barry; Caroline D. Robson; Flavia M. Facio; Carol Van Ryzin; Wai-Man Chan; Tanya J. Lehky; Audrey Thurm; Christopher Zalewski; Kelly A. King; Carmen Brewer; Konstantinia Almpani; et al. (Human Genetics, 2021)

Reproductive trade-offs in the colorado checkered whiptail lizard (Aspidoscelis neotesselatus): an examination of the relationship between clutch and follicle size - Hannah E. Caracalas; S. S. French; S. B. Hudson; B. M. Kluever; A. C. Webb; D. Eifler; A. J. Lehmicke; L. M. Aubry (Evolutionary Ecology, 2021)

Early inflammation precedes cardiac fibrosis and heart failure in desmoglein 2 murine model of arrhythmogenic cardiomyopathy - K. E. Ng; P. J. Delaney; D. Thenet; S. Murtough; C. M. Webb; N. Zaman; E. Tsisanova; G. Mastroianni; S. L. M. Walker; J. D. Westaby; D. J. Pennington; R. Pink; et al. (Cell and Tissue Research, 2021)
The study of a desmoglein 2 murine model of arrhythmogenic cardiomyopathy revealed cardiac inflammation as a key early event leading to fibrosis. Arrhythmogenic cardiomyopathy (AC) is an inherited heart muscle disorder leading to ventricular arrhythmias and heart failure due to abnormalities in the cardiac desmosome. We examined how loss of desmoglein 2 ( Dsg2 ) in the young murine heart leads to development of AC. Apoptosis was an early cellular phenotype, and RNA sequencing analysis revealed early activation of inflammatory-associated pathways in Dsg2 -null ( Dsg2 −/− ) hearts at postnatal day 14 (2 weeks) that were absent in the fibrotic heart of adult mice (10 weeks). This included upregulation of iRhom2/ADAM17 and its associated pro-inflammatory cytokines and receptors such as TNFα, IL6R and IL-6. Furthermore, genes linked to specific macrophage populations were also upregulated. This suggests cardiomyocyte stress triggers an early immune response to clear apoptotic cells allowing tissue remodelling later on in the fibrotic heart. Our analysis at the early disease stage suggests cardiac inflammation is an important response and may be one of the mechanisms responsible for AC disease progression.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Trophic cascade driven by behavioral fine‐tuning as naïve prey rapidly adjust to a novel predator - Chris J. Jolly; Adam S. Smart; John Moreen; Jonathan K. Webb; Graeme R. Gillespie; Ben L. Phillips (Ecology, 2021)
The arrival of novel predators can trigger trophic cascades driven by shifts in prey numbers. Predators also elicit behavioral change in prey populations, via phenotypic plasticity and/or rapid evolution, and such changes may also contribute to trophic cascades. Here, we document rapid demographic and behavioral changes in populations of a prey species (grassland melomys Melomys burtoni , a granivorous rodent) following the introduction of a novel marsupial predator (northern quoll Dasyurus hallucatus ). Within months of quolls appearing, populations of melomys exhibited reduced survival and population declines relative to control populations. Quoll‐invaded populations were also significantly shyer than nearby, quoll‐free populations of conspecifics. This rapid but generalized response to a novel threat was replaced over the following 2 yr with more threat‐specific antipredator behaviors (i.e., predator‐scent aversion). Predator‐exposed populations, however, remained more neophobic than predator‐free populations throughout the study. These behavioral responses manifested rapidly in changed rates of seed predation by melomys across treatments. Quoll‐invaded melomys populations exhibited lower per‐capita seed take rates, and rapidly developed an avoidance of seeds associated with quoll scent, with discrimination playing out over a spatial scale of tens of meters. Presumably the significant and novel predation pressure induced by quolls drove melomys populations to fine‐tune behavioral responses to be more predator specific through time. These behavioral shifts could reflect individual plasticity (phenotypic flexibility) in behavior or may be adaptive shifts from natural selection imposed by quoll predation. Our study provides a rare insight into the rapid ecological and behavioral shifts enacted by prey to mitigate the impacts of a novel predator and shows that trophic cascades can be strongly influenced by behavioral as well as numerical responses.

Correction to: Synchronized broadcast spawning by six invertebrates (Echinodermata and Mollusca) in the north-western Red Sea - Alice E. Webb; Aschwin H. Engelen; Jessica Bouwmeester; Inge van Dijk; Esmee Geerken; Julie Lattaud; Dario Engelen; Bernadette S. de Bakker; Didier M. de Bakker (Marine Biology, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Synchronized broadcast spawning by six invertebrates (Echinodermata and Mollusca) in the north-western Red Sea - Alice E. Webb; Aschwin H. Engelen; Jessica Bouwmeester; Inge van Dijk; Esmee Geerken; Julie Lattaud; Dario Engelen; Bernadette S. de Bakker; Didier M. de Bakker (Marine Biology, 2021)
On the evenings of June 11 and 12, 2019, 5 and 6 days before full moon, broadcast spawning by four echinoderm species and two mollusc species was observed on the Marsa Shagra reef, Egypt (25° 14′ 44.2" N, 34° 47′ 49.0" E). Water temperature was 28 °C and the invertebrates were observed at 2–8 m depth. The sightings included a single basket star Astroboa nuda (Lyman 1874), 2 large Tectus dentatus (Forskal 1775) sea snails, 14 individuals of the Leiaster cf. leachi (Gray 1840) sea star and 1 Mithrodia clavigera (Lamarck 1816) sea star, 3 Pearsonothuria graeffei (Semper 1868) sea cucumbers, and 2 giant clams, Tridacna maxima (Röding 1798). The observations presented here provide relevant information on broadcast spawning of non-coral invertebrate taxa in the Red Sea, where spawning is considerably less well documented than in other tropical geographical regions such as the Indo-Pacific and Caribbean.

What’s hot and what’s not: Making sense of biodiversity ‘hotspots’ - Murray S. A. Thompson; Elena Couce; Thomas J. Webb; Miriam Grace; Keith M. Cooper; Michaela Schratzberger (Global Change Biology, 2021)
Conserving biogeographic regions with especially high biodiversity, known as biodiversity ‘hotspots’, is intuitive because finite resources can be focussed towards manageable units. Yet, biodiversity, environmental conditions and their relationship are more complex with multidimensional properties. Assessments which ignore this risk failing to detect change, identify its direction or gauge the scale of appropriate intervention. Conflicting concepts which assume assemblages as either sharply delineated communities or loosely collected species have also hampered progress in the way we assess and conserve biodiversity. We focus on the marine benthos where delineating manageable areas for conservation is an attractive prospect because it holds most marine species and constitutes the largest single ecosystem on earth by area. Using two large UK marine benthic faunal datasets, we present a spatially gridded data sampling design to account for survey effects which would otherwise be the principal drivers of diversity estimates. We then assess γ‐diversity (regional richness) with diversity partitioned between α (local richness) and β (dissimilarity), and their change in relation to covariates to test whether defining and conserving biodiversity hotspots is an effective conservation strategy in light of the prevailing forces structuring those assemblages. α‐, β‐ and γ‐diversity hotspots were largely inconsistent with each metric relating uniquely to the covariates, and loosely collected species generally prevailed with relatively few distinct assemblages. Hotspots could therefore be an unreliable means to direct conservation efforts if based on only a component part of diversity. When assessed alongside environmental gradients, α‐, β‐ and γ‐diversity provide a multidimensional but still intuitive perspective of biodiversity change that can direct conservation towards key drivers and the appropriate scale for intervention. Our study also highlights possible temporal declines in species richness over 30 years and thus the need for future integrated monitoring to reveal the causal drivers of biodiversity change.

Short‐term homeostatic regulation of blood/interstitial fluid Ca 2+ concentration by the scales of anadromous sea trout Salmo trutta L. during smoltification and migration - Leanna Jamieson; Angel Waters; Kaitlyn E. Ho; Harvey Y. S. Chan; Jacky T. Hung; Sarah E. Webb; Ching Man Chan; Alan M. Shipley; John G. Williamson; Jon Beer; Chevonne Angus; Andrew L. Miller (Journal of Fish Biology, 2021)
The elasmoid scales of anadromous sea trout Salmo trutta L. represent a significant internal reservoir of Ca 2+ . Although more is known about long‐term remodelling of scales in response to calciotropic challenges encountered during smoltification and migration, very little is known about the contribution made by scales to the short‐term, minute‐to‐minute regulation of Ca 2+ homeostasis in the extracellular fluid (ECF) during these phases of the life cycle. This gap in the knowledge is partly due to the technical challenges involved in measuring small Ca 2+ fluxes around the scales of live fish in real time. Here, this study describes exfoliating, mounting and culturing scales and their resident cells from parr, smolt and adult sea trout from a freshwater environment, as well as from adult sea trout caught in sea or brackish water. All the scales were then examined using an extracellular, non‐invasive, surface‐scanning Ca 2+ ‐sensitive microelectrode. The authors quantified the Ca 2+ fluxes, in the absence of any systemic or local regulators, into and out of scales on both the episquamal and hyposquamal sides under different extracellular calcemic challenges set to mimic a variety of ECF‐Ca 2+ concentrations. Scales from the life‐cycle stages as well as from adult fish taken from sea, brackish or fresh water all showed a consistent efflux or influx of Ca 2+ under hypo‐ or hypercalcemic conditions, respectively. What were considered to be isocalcemic conditions resulted in minimal flux of Ca 2+ in either direction, or in the case of adult scales, a consistent but small influx. Indeed, adult scales appeared to display the largest flux densities in either direction. These new data extend the current understanding of the role played by fish scales in the short‐term, minute‐to‐minute homeostatic regulation of ECF‐Ca 2+ concentration, and are similar to those recently reported from zebrafish Danio rerio scales. This suggests that this short‐term regulatory response might be a common feature of teleost scales.

Competing reproductive and physiological investments in an all-female lizard, the Colorado checkered whiptail - Lise M. Aubry; Spencer B. Hudson; Bryan M. Kluever; Alison C. Webb; Susannah S. French (Evolutionary Ecology, 2020)

Intermittent but not continuous access to cocaine produces individual variability in addiction susceptibility in rats - A. F. Garcia; I. G. Webb; L. M. Yager; M. B. Seo; S. M. Ferguson (Psychopharmacology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Genetic structures across a biogeographical barrier reflect dispersal potential of four Southeast Asian mangrove plant species - Alison K. S. Wee; Annika M. E. Noreen; Junya Ono; Koji Takayama; Prakash P. Kumar; Hugh T. W. Tan; Mohd N. Saleh; Tadashi Kajita; Edward L. Webb (Journal of Biogeography, 2020)
Aim Biogeographical barriers restrict the movement of individuals, resulting in population divergence, genetic differentiation, endemism and speciation. Yet, some barriers demonstrate unequal effect across species depending on species dispersal, which manifests in varying genetic structure. We test the hypotheses that the genetic structure of four coastal mangrove species would reflect differences in dispersal potential across the Malay Peninsula, a major biogeographical barrier in the Indo‐West Pacific region. Location East and west coasts of the Malay Peninsula. Taxon Mangrove trees Avicennia alba , Sonneratia alba , Bruguiera gymnorhiza and Rhizophora mucronata. Methods For each species, we characterized genetic structure and gene flow using 7–12 species‐specific nuclear microsatellite markers. We tested for east–west genetic differentiation across the peninsula, a stepping‐stone migration pattern, and assessed the proportion of recent dispersal and direction of historical migration along the Malacca Strait. Results Significant east–west genetic differentiation across the peninsula was observed in A. alba , S. alba and B. gymnorhiza , and the effect was most pronounced for the two species with lower dispersal potential ( A. alba , S. alba ). In contrast, the two species with higher dispersal potential ( B. gymnorhiza and R. mucronata ) exhibited much higher proportion of recent inter‐population migration along the Malacca Strait. The signature of historical colonization from refugia in the Andaman Sea (north‐to‐south migration along the Malacca Strait) predominated for A. alba and S. alba. Historical south–north migration predominated for R. mucronata and B. gymnorhiza . Main conclusions This study implicated dispersal potential as a cause of varying mangrove species genetic structure across a biogeographical barrier. The Malay Peninsula functions as a filter to gene flow rather than a barrier. The genetic structure in mangrove species with a higher dispersal potential is more congruent with contemporary gene flow while that of species with a lower dispersal potential reflects historical processes. Our findings hint at the role of dispersal potential as a predictor of gene flow in mangroves.

A trophic cascade initiated by an invasive vertebrate alters the structure of native reptile communities - Benjamin Feit; Tim Dempster; Tim S. Jessop; Jonathan K. Webb; Mike Letnic (Global Change Biology, 2020)
Invasive vertebrates are frequently reported to have catastrophic effects on the populations of species which they directly impact. It follows then, that if invaders exert strong suppressive effects on some species then other species will indirectly benefit due to ecological release from interactions with directly impacted species. However, evidence that invasive vertebrates trigger such trophic cascades and alter community structure in terrestrial ecosystems remains rare. Here, we ask how the cane toad, a vertebrate invader that is toxic to many of Australia's vertebrate predators, influences lizard assemblages in a semi‐arid rangeland. In our study area, the density of cane toads is influenced by the availability of water accessible to toads. We compared an index of the abundance of sand goannas, a large predatory lizard that is susceptible to poisoning by cane toads and the abundances of four lizard families preyed upon by goannas (skinks, pygopods, agamid lizards and geckos) in areas where cane toads were common or rare. Consistent with the idea that suppression of sand goannas by cane toads initiates a trophic cascade, goanna activity was lower and small lizards were more abundant where toads were common. The hypothesis that suppression of sand goannas by cane toads triggers a trophic cascade was further supported by our findings that small terrestrial lizards that are frequently preyed upon by goannas were more affected by toad abundance than arboreal geckos, which are rarely consumed by goannas. Furthermore, the abundance of at least one genus of terrestrial skinks benefitted from allogenic ecosystem engineering by goannas where toads were rare. Overall, our study provides evidence that the invasion of ecosystems by non‐native species can have important effects on the structure and integrity of native communities extending beyond their often most obvious and frequently documented direct ecological effects.

Metabolic Niches and Biodiversity: A Test Case in the Deep Sea Benthos - Craig R. McClain; Thomas J. Webb; Clifton C. Nunnally; S. River Dixon; Seth Finnegan; James A. Nelson (Frontiers in Marine Science, 2020)

Assessment of the Utility of the Oral Fluid and Plasma Proteomes for Hydrocodone Exposure - Brooke L. Deatherage Kaiser; Jon M. Jacobs; Athena A. Schepmoes; Heather M. Brewer; Bobbie-Jo M. Webb-Robertson; Sandra Valtier; Vikhyat S. Bebarta; Joshua N. Adkins (Journal of Medical Toxicology, 2020)

Re-examination of the effects of food abundance on jaw plasticity in purple sea urchins - Maya S. deVries; Summer J. Webb; Jennifer R. A. Taylor (Marine Biology, 2019)

Co-development of a climate change decision support framework through engagement with stakeholders - Anne M. Leitch; J. P. Palutikof; D. Rissik; S. L. Boulter; Fahim N. Tonmoy; S. Webb; A. C. Perez Vidaurre; M. C. Campbell (Climatic Change, 2019)

CoastAdapt: an adaptation decision support framework for Australia’s coastal managers - J. P. Palutikof; D. Rissik; S. Webb; Fahim N. Tonmoy; S. L. Boulter; Anne M. Leitch; A. C. Perez Vidaurre; M. J. Campbell (Climatic Change, 2019)

Overcoming knowledge barriers to adaptation using a decision support framework - J. P. Palutikof; Anne M. Leitch; D. Rissik; S. L. Boulter; M. J. Campbell; A. C. Perez Vidaurre; S. Webb; Fahim N. Tonmoy (Climatic Change, 2019)

Uncertainty in water resources: introduction to the special column - S. R. Fassnacht; R. W. Webb; M. Ma (Frontiers of Earth Science, 2018)

Human Neural Stem Cell Extracellular Vesicles Improve Tissue and Functional Recovery in the Murine Thromboembolic Stroke Model - Robin L. Webb; Erin E. Kaiser; Shelley L. Scoville; Tyler A. Thompson; Sumbul Fatima; Chirayukumar Pandya; Karishma Sriram; Raymond L. Swetenburg; Kumar Vaibhav; Ali S. Arbab; Babak Baban; Krishnan M. Dhandapani; et al. (Translational Stroke Research, 2018)

Replication of a rare risk haplotype on 1p36.33 for autism spectrum disorder - N. H. Chapman; R. A. Bernier; S. J. Webb; J. Munson; E. M. Blue; D.-H. Chen; E. Heigham; W. H. Raskind; Ellen M. Wijsman (Human Genetics, 2018)

Invasive cane toads might initiate cascades of direct and indirect effects in a terrestrial ecosystem - Benjamin Feit; Christopher E. Gordon; Jonathan K. Webb; Tim S. Jessop; Shawn W. Laffan; Tim Dempster; Mike Letnic (Biological Invasions, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

A three-dimensional numerical study of river plume mixing processes in Otsuchi Bay, Japan - Kaushik Sasmal; Eiji Masunaga; Adrean Webb; Oliver B. Fringer; Edward S. Gross; Matthew D. Rayson; Hidekatsu Yamazaki (Journal of Oceanography, 2018)

Regional forcing explains local species diversity and turnover on tropical islands - Thomas Ibanez; Gunnar Keppel; Cláudia Baider; Chris Birkinshaw; Heike Culmsee; Susan Cordell; F. B. Vincent Florens; Janet Franklin; Christian P. Giardina; Thomas W. Gillespie; Melinda Laidlaw; Creighton M. Litton; et al. (Global Ecology and Biogeography, 2018)
Aim To determine the role of regional forcing on plot‐level species diversity and composition, and to quantify the relative importance of biogeographical and climatic factors in explaining woody plant diversity and composition at the local‐, island‐ and archipelago‐scale. Location Forty‐one tropical islands of the Indo‐Pacific region from Madagascar to Hawai‘i Island. Methods We analysed the diversity and composition of tropical woody plant communities located across 113 plots, 41 islands and 19 archipelagos. We used generalized linear mixed‐effects models and generalized dissimilarity models to determine the role of regional forcing at the island and archipelago scale and to assess the relative importance of biogeographical (area and isolation of islands or archipelagos, geographical distance between plots) and climatic factors in explaining differences in local diversity and composition (species turnover). Analyses were conducted at different geographical scales (local, island and archipelago) and taxonomic levels (species, genus and family). Results Variation in local (plot‐level) diversity (as species density, the number of species per 100 woody plants) was primarily explained by island and archipelago identity. Maximum species density was positively correlated with the area of an island (or archipelago) and negatively correlated with the isolation of an archipelago. Local climatic variability was also a significant predictor of species density, but less important than regional forcing. Climate variables explained Main conclusions Regional forcing was the key driver of local diversity and composition on islands. Island area and archipelago isolation are likely driving local diversity through their effects on the pool of island species. Geographical distance between plots is the main factor explaining species turnover, while at higher taxonomic levels, climatic factors and niche conservatism are the main drivers.

Metabolic responses to different immune challenges and varying resource availability in the side-blotched lizard (Uta stansburiana) - Geoffrey D. Smith; Lorin A. Neuman-Lee; Alison C. Webb; Michael J. Angilletta; Dale F. DeNardo; Susannah S. French (Journal of Comparative Physiology B, 2017)

Acute high-caffeine exposure increases autophagic flux and reduces protein synthesis in C2C12 skeletal myotubes - M. A. Hughes; R. M. Downs; G. W. Webb; C. L. Crocker; S. T. Kinsey; Bradley L. Baumgarner (Journal of Muscle Research and Cell Motility, 2017)

Inferring infection hazard in wildlife populations by linking data across individual and population scales - Kim M. Pepin; Shannon L. Kay; Ben D. Golas; Susan S. Shriner; Amy T. Gilbert; Ryan S. Miller; Andrea L. Graham; Steven Riley; Paul C. Cross; Michael D. Samuel; Mevin B. Hooten; Jennifer A. Hoeting; et al. (Ecology Letters, 2017)
Our ability to infer unobservable disease‐dynamic processes such as force of infection (infection hazard for susceptible hosts) has transformed our understanding of disease transmission mechanisms and capacity to predict disease dynamics. Conventional methods for inferring FOI estimate a time‐averaged value and are based on population‐level processes. Because many pathogens exhibit epidemic cycling and FOI is the result of processes acting across the scales of individuals and populations, a flexible framework that extends to epidemic dynamics and links within‐host processes to FOI is needed. Specifically, within‐host antibody kinetics in wildlife hosts can be short‐lived and produce patterns that are repeatable across individuals, suggesting individual‐level antibody concentrations could be used to infer time since infection and hence FOI . Using simulations and case studies (influenza A in lesser snow geese and Yersinia pestis in coyotes), we argue that with careful experimental and surveillance design, the population‐level FOI signal can be recovered from individual‐level antibody kinetics, despite substantial individual‐level variation. In addition to improving inference, the cross‐scale quantitative antibody approach we describe can reveal insights into drivers of individual‐based variation in disease response, and the role of poorly understood processes such as secondary infections, in population‐level dynamics of disease.

The fungal cultivar of leaf‐cutter ants produces specific enzymes in response to different plant substrates - Lily Khadempour; Kristin E. Burnum‐Johnson; Erin S. Baker; Carrie D. Nicora; Bobbie‐Jo M. Webb‐Robertson; Richard A. White; Matthew E. Monroe; Eric L. Huang; Richard D. Smith; Cameron R. Currie (Molecular Ecology, 2016)
Herbivores use symbiotic microbes to help derive energy and nutrients from plant material. Leaf‐cutter ants are a paradigmatic example, cultivating their mutualistic fungus Leucoagaricus gongylophorus on plant biomass that workers forage from a diverse collection of plant species. Here, we investigate the metabolic flexibility of the ants’ fungal cultivar for utilizing different plant biomass. Using feeding experiments and a novel approach in metaproteomics, we examine the enzymatic response of L. gongylophorus to leaves, flowers, oats or a mixture of all three. Across all treatments, our analysis identified and quantified 1766 different fungal proteins, including 161 putative biomass‐degrading enzymes. We found significant differences in the protein profiles in the fungus gardens of subcolonies fed different plant substrates. When provided with leaves or flowers, which contain the majority of their energy as recalcitrant plant polymers, the fungus gardens produced more proteins predicted to break down cellulose: endoglucanase, exoglucanase and β‐glucosidase. Further, the complete metaproteomes for the leaves and flowers treatments were very similar, while the mixed substrate treatment closely resembled the treatment with oats alone. This indicates that when provided a mixture of plant substrates, fungus gardens preferentially break down the simpler, more digestible substrates. This flexible, substrate‐specific enzymatic response of the fungal cultivar allows leaf‐cutter ants to derive energy from a wide range of substrates, which likely contributes to their ability to be dominant generalist herbivores.

Bruguiera hainesii, a critically endangered mangrove species, is a hybrid between B. cylindrica and B. gymnorhiza (Rhizophoraceae) - Junya Ono; Jean W. H. Yong; Koji Takayama; Mohd Nazre Bin Saleh; Alison K. S. Wee; Takeshi Asakawa; Orlex Baylen Yllano; Severino G. Salmo; Monica Suleiman; Nguyen Xuan Tung; Khin Khin Soe; Sankararamasubramanian Halasya Meenakshisundaram; et al. (Conservation Genetics, 2016)

Moderate-intensity exercise alters markers of alternative activation in circulating monocytes in females: a putative role for PPARγ - J. S. Ruffino; N. A. Davies; K. Morris; M. Ludgate; L. Zhang; R. Webb; A. W. Thomas (European Journal of Applied Physiology, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Expression and reconstitution of the bioluminescent Ca2+ reporter aequorin in human embryonic stem cells, and exploration of the presence of functional IP3 and ryanodine receptors during the early stages of their differentiation into cardiomyocytes - Harvey Y. S. Chan; Man Chun Cheung; Yi Gao; Andrew L. Miller; Sarah E. Webb (Science China Life Sciences, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Causal modelling applied to the risk assessment of a wastewater discharge - Warren L. Paul; Pat A. Rokahr; Jeff M. Webb; Gavin N. Rees; Tim S. Clune (Environmental Monitoring and Assessment, 2016)

Opportunities and Challenges in the Design and Analysis of Biomass Supply Chains - Pasi T. Lautala; Michael R. Hilliard; Erin Webb; Ingrid Busch; J. Richard Hess; Mohammad S. Roni; Jorge Hilbert; Robert M. Handler; Roger Bittencourt; Amir Valente; Tuuli Laitinen (Environmental Management, 2015)

Network analysis of host–virus communities in bats and rodents reveals determinants of cross‐species transmission - Angela D. Luis; Thomas J. O'Shea; David T. S. Hayman; James L. N. Wood; Andrew A. Cunningham; Amy T. Gilbert; James N. Mills; Colleen T. Webb (Ecology Letters, 2015)
Bats are natural reservoirs of several important emerging viruses. Cross‐species transmission appears to be quite common among bats, which may contribute to their unique reservoir potential. Therefore, understanding the importance of bats as reservoirs requires examining them in a community context rather than concentrating on individual species. Here, we use a network approach to identify ecological and biological correlates of cross‐species virus transmission in bats and rodents, another important host group. We show that given our current knowledge the bat viral sharing network is more connected than the rodent network, suggesting viruses may pass more easily between bat species. We identify host traits associated with important reservoir species: gregarious bats are more likely to share more viruses and bats which migrate regionally are important for spreading viruses through the network. We identify multiple communities of viral sharing within bats and rodents and highlight potential species traits that can help guide studies of novel pathogen emergence.

Mouse genome annotation by the RefSeq project - Kelly M. McGarvey; Tamara Goldfarb; Eric Cox; Catherine M. Farrell; Tripti Gupta; Vinita S. Joardar; Vamsi K. Kodali; Michael R. Murphy; Nuala A. O’Leary; Shashikant Pujar; Bhanu Rajput; Sanjida H. Rangwala; et al. (Mammalian Genome, 2015)
Complete and accurate annotation of the mouse genome is critical to the advancement of research conducted on this important model organism. The National Center for Biotechnology Information (NCBI) develops and maintains many useful resources to assist the mouse research community. In particular, the reference sequence (RefSeq) database provides high-quality annotation of multiple mouse genome assemblies using a combinatorial approach that leverages computation, manual curation, and collaboration. Implementation of this conservative and rigorous approach, which focuses on representation of only full-length and non-redundant data, produces high-quality annotation products. RefSeq records explicitly link sequences to current knowledge in a timely manner, updating public records regularly and rapidly in response to nomenclature updates, addition of new relevant publications, collaborator discussion, and user feedback. Whole genome re-annotation is also conducted at least every 12–18 months, and often more frequently in response to assembly updates or availability of informative data. This article highlights key features and advantages of RefSeq genome annotation products and presents an overview of NCBI processes to generate these data. Further discussion of NCBI’s resources highlights useful features and the best methods for accessing our data.

Effects of broodstock diets on growth of larval Atlantic cod (Gadus morhua L.) - Juan Carlos Pérez-Casanova; Matthew Webb; Lynn Lush; Christopher Parrish; Isabel A. S. F. Costa; Dounia Hamoutene (Aquaculture International, 2015)

Volumetric Fracture Intensity Measurement for Improved Rock Mass Characterisation and Fragmentation Assessment in Block Caving Operations - S. Rogers; D. Elmo; G. Webb; A. Catalan (Rock Mechanics and Rock Engineering, 2015)

The diurnal cycle of marine cloud feedback in climate models - Mark J. Webb; Adrian P. Lock; Alejandro Bodas-Salcedo; Sandrine Bony; Jason N. S. Cole; Tsuyoshi Koshiro; Hideaki Kawai; Carlo Lacagnina; Frank M. Selten; Romain Roehrig; Bjorn Stevens (Climate Dynamics, 2015)

Erratum to: Methods to account for tree-scale variability in soil and plant-related parameters in oil palm plantations - P. N. Nelson; M. J. Webb; M. Banabas; S. Nake; I. Goodrick; J. Gordon; D. O’Grady; B. Dubos (Plant and Soil, 2014)

Oceanic currents, not land masses, maintain the genetic structure of the mangrove Rhizophora mucronata Lam. (Rhizophoraceae) in Southeast Asia - Alison K. S. Wee; Koji Takayama; Takeshi Asakawa; Bijoy Thompson; Onrizal; Sarawood Sungkaew; Nguyen Xuan Tung; M. Nazre; Khin Khin Soe; Hugh T. W. Tan; Yasuyuki Watano; Shigeyuki Baba; et al. (Journal of Biogeography, 2014)
Aim Mangroves are intertidal plants with sea‐dispersed propagules, hence their population structure can offer valuable insights into the biogeographical processes driving population subdivision in coastal species. In this study, we used molecular markers and ocean circulation simulations to examine the effects of ocean currents and land masses on the genetic structure of the major mangrove species Rhizophora mucronata . Location Southeast Asia. Methods We assessed the genetic structure of 13 R. mucronata populations from continental Southeast Asia and Sumatra using 10 microsatellite loci. We first examined the relative effects of geographical distance and land mass (the Malay Peninsula) in shaping the genetic structure of R. mucronata in Southeast Asia. We then characterized the genetic structure of R. mucronata and compared it to the simulated ocean circulation patterns within our study region. Results Despite the low genetic diversity, significant genetic structuring was detected across R. mucronata populations. Contrary to observations on other mangrove species, genetic differentiation in R. mucronata was not found across the coasts of the Malay Peninsula, nor was it correlated with geographical distance. Instead, the most distinct genetic discontinuity was found at the boundary between the Andaman Sea and the Malacca Strait, and this can be explained by the prevailing ocean currents in this region. Main conclusions Our study presents novel evidence that the genetic structure of R. mucronata is maintained by ocean current‐facilitated propagule dispersal.

Methods to account for tree-scale variability in soil- and plant-related parameters in oil palm plantations - P. N. Nelson; M. J. Webb; M. Banabas; S. Nake; I. Goodrick; J. Gordon; D. O’Grady; B. Dubos (Plant and Soil, 2014)

Development of 11 polymorphic microsatellite markers for Xylocarpus granatum (Meliaceae) using next-generation sequencing technology - Yuki Tomizawa; Yoshimi Shinmura; Alison K. S. Wee; Koji Takayama; Takeshi Asakawa; Orlex Baylen Yllano; Severino Garengo Salmo; Erwin Riyanto Ardli; Nguyen Xuan Tung; Norhaslinda Binti Malekal; Onrizal; Sankararamasubramanian Halasya Meenakshisundaram; et al. (Conservation Genetics Resources, 2013)

Reliability and importance of structural diversity of climate model ensembles - Tokuta Yokohata; James D. Annan; Matthew Collins; Charles S. Jackson; Hideo Shiogama; Masahiro Watanabe; Seita Emori; Masakazu Yoshimori; Manabu Abe; Mark J. Webb; Julia C. Hargreaves (Climate Dynamics, 2013)

Comparative life histories of fishes in the genus Phallichthys (Pisces: Poeciliidae) - J. U. Regus; J. B. Johnson; S. A. Webb; D. N. Reznick (Journal of Fish Biology, 2013)
This study presents a description of the life histories of all four species of the genus Phallichthys , found primarily in the Atlantic slope of Central America (ranging from northern Panama to Mexico), based on a combination of data collected from preserved and living specimens. All species produced a single litter of offspring before developing another brood ( i.e . no superfoetation). In the laboratory, the mean time interval between successive litters ranged from 24 to 48 days, further suggesting that they lack superfoetation. Embryos lose from 15 to 65% of their dry mass during development, meaning all or the large majority of resources required for development are provided prior to fertilization (lecithotrophy). All mature male size distributions were platykurtotic and appeared either bimodal or multimodal. Multimodal and skewed size distributions have been associated with genetic polymorphisms for size at maturity in other species of Poeciliidae. As the sister clade to Phallichthys includes genera in which all species have superfoetation ( Neoheterandria and Poeciliopsis ), these results suggest that their common ancestor with Phallichthys also had superfoetation and that the trait has been lost.

A loop-mediated isothermal amplification-based method for confirmation of Guignardia citricarpa in citrus black spot lesions - J. A. Tomlinson; S. Ostoja-Starzewska; K. Webb; J. Cole; A. Barnes; M. Dickinson; N. Boonham (European Journal of Plant Pathology, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Scaling of standard metabolic rate in estuarine crocodiles Crocodylus porosus - Roger S. Seymour; C. M. Gienger; Matthew L. Brien; Christopher R. Tracy; S. Charlie Manolis; Grahame J. W. Webb; Keith A. Christian (Journal of Comparative Physiology B, 2013)

Filtration of sea louse, L epeophtheirus salmonis , copepodids by the blue mussel, M ytilus edulis , and the A tlantic sea scallop, P lacopecten magellanicus , under different flow, light and copepodid‐density regimes - A Bartsch; S M C Robinson; M Liutkus; K P Ang; J Webb; C M Pearce (Journal of Fish Diseases, 2013)
Population management of L epeophtheirus salmonis in C anada currently relies on chemotherapeutants to remove attached stages of the ectoparasite. However, some populations of L . salmonis are developing resistance to chemotherapeutants making alternate management measures necessary. This article explores the ability of filter‐feeding shellfish [ i.e . blue mussels ( Mytilus edulis ) and A tlantic sea scallops ( P lacopecten magellanicus )] to consume the copepodid stages of L . salmonis in the laboratory under static and flowing water conditions, with variable copepodid densities, and with the aid of a light attractant. M ytilus edulis consumed copepodids under both static and flowing water conditions, and the proportion of individuals ingested was similar at low and high copepodid densities, suggesting that M . edulis was not saturated at the concentrations tested. Also, M . edulis consumed more copepodids when a light attractant was present, suggesting that lights may be useful to concentrate widely dispersed copepodids around cultured shellfish in the field. Finally, P . magellanicus consumed the same number of copepodids as an equivalent total wet weight of M . edulis . During each of the four separate experiments, shellfish consumed between 18 and 38% of the copepodids presented per hour, suggesting that both species are well suited for low level removal of copepodids over time.

Isolation and characterization of 14 microsatellite markers for Rhizophora mucronata (Rhizophoraceae) and their potential use in range-wide population studies - Yoshimi Shinmura; Alison K. S. Wee; Koji Takayama; Sankararamasubramanian Halasya Meenakshisundaram; Takeshi Asakawa; Onrizal; Bayu Adjie; Erwin Riyanto Ardli; Sarawood Sungkaew; Norhaslinda Binti Malekal; Nguyen Xuan Tung; Severino G. Salmo III; et al. (Conservation Genetics Resources, 2012)

Model‐guided fieldwork: practical guidelines for multidisciplinary research on wildlife ecological and epidemiological dynamics - Olivier Restif; David T. S. Hayman; Juliet R. C. Pulliam; Raina K. Plowright; Dylan B. George; Angela D. Luis; Andrew A. Cunningham; Richard A. Bowen; Anthony R. Fooks; Thomas J. O'Shea; James L. N. Wood; Colleen T. Webb (Ecology Letters, 2012)
Infectious disease ecology has recently raised its public profile beyond the scientific community due to the major threats that wildlife infections pose to biological conservation, animal welfare, human health and food security. As we start unravelling the full extent of emerging infectious diseases, there is an urgent need to facilitate multidisciplinary research in this area. Even though research in ecology has always had a strong theoretical component, cultural and technical hurdles often hamper direct collaboration between theoreticians and empiricists. Building upon our collective experience of multidisciplinary research and teaching in this area, we propose practical guidelines to help with effective integration among mathematical modelling, fieldwork and laboratory work. Modelling tools can be used at all steps of a field‐based research programme, from the formulation of working hypotheses to field study design and data analysis. We illustrate our model‐guided fieldwork framework with two case studies we have been conducting on wildlife infectious diseases: plague transmission in prairie dogs and lyssavirus dynamics in A merican and A frican bats. These demonstrate that mechanistic models, if properly integrated in research programmes, can provide a framework for holistic approaches to complex biological systems.

Consensus Paper: Pathological Role of the Cerebellum in Autism - S. Hossein Fatemi; Kimberly A. Aldinger; Paul Ashwood; Margaret L. Bauman; Charles D. Blaha; Gene J. Blatt; Abha Chauhan; Ved Chauhan; Stephen R. Dager; Price E. Dickson; Annette M. Estes; Dan Goldowitz; et al. (The Cerebellum, 2012)

Development and characterization of 15 polymorphic microsatellite loci in Sonneratia alba (Lythraceae) using next-generation sequencing - Yoshimi Shinmura; Alison K. S. Wee; Koji Takayama; Takeshi Asakawa; Orlex Baylen Yllano; Severino G. Salmo; Erwin Riyanto Ardli; Nguyen Xuan Tung; Norhaslinda Binti Malekal; Onrizal; Sankararamasubramanian Halasya Meenakshisundaram; Sarawood Sungkaew; et al. (Conservation Genetics Resources, 2012)

Ti diffusion in quartz inclusions: implications for metamorphic time scales - Frank S. Spear; Kyle T. Ashley; Laura E. Webb; Jay B. Thomas (Contributions to Mineralogy and Petrology, 2012)

Reliability of multi-model and structurally different single-model ensembles - Tokuta Yokohata; James D. Annan; Matthew Collins; Charles S. Jackson; Michael Tobis; Mark J. Webb; Julia C. Hargreaves (Climate Dynamics, 2012)

The Control of an Invasive Bivalve, Corbicula fluminea, Using Gas Impermeable Benthic Barriers in a Large Natural Lake - Marion E. Wittmann; Sudeep Chandra; John E. Reuter; S. Geoffrey Schladow; Brant C. Allen; Katie J. Webb (Environmental Management, 2012)

The toxic effects of three dinoflagellate species from the genus Karenia on invertebrate larvae and finfish - F Shi; P McNabb; L Rhodes; P Holland; S Webb; J Adamson; A Immers; R Gooneratne; J Holland (New Zealand Journal of Marine and Freshwater Research, 2012)
Three species of Kareniaceae, Karenia brevis , Karenia brevisulcata and Karenia mikimotoi were assessed for toxicity to juvenile Chinook salmon ( Oncorhynchus tshawytscha ), snapper ( Pagrus auratus ) and six species of marine invertebrate larvae (Greenshell TM mussel, pacific oyster, paua [New Zealand abalone], sea slug, sea urchin and brine shrimp). Karenia brevis was ichthyotoxic to juvenile salmon with a LT 50 of 0.75 h at 0.18 × 10 6 cells L –1 but juvenile snapper were less sensitive (LT 50 of 4.5 h at 5.9 × 10 6 cells L –1 ). Karenia brevisulcata also showed differential toxicity to juvenile salmon and snapper with LT 50 of 0.48 h at 11 × 10 6 cells L –1 and 7.5 h at 16 × 10 6 cells L –1 respectively. However, no acute symptoms were observed in the fish following 48 h exposure to K. mikimotoi at 3.4 × 10 6 cells L –1 . Karenia brevis at the highest level tested (8.7 × 10 6 cells L –1 ) did not cause observable symptoms in any of the invertebrate larvae over 24 h. Karenia mikimotoi only affected paua larvae (LT 50 10 h at 12 × 10 6 cells L –1 ). Karenia brevisulcata was highly toxic to mussel, sea urchin and paua larvae (LT 50 1–6.1 h at 7.5–9.6 × 10 6 cells L –1 ), toxic to sea slug and oyster larvae (LT 50 6 h at 80 × 10 6 cells L –1 and 9.2 h at 34 × 10 6 cells L –1 respectively) but did not affect brine shrimp. Analysis of test cultures by liquid chromatography‐mass spectrometry confirmed that K. brevis produced brevetoxins (52 pg cell –1 ; mainly brevetoxin‐2). Karenia brevisulcata produced brevisulcatic acids (BSXs) and the more toxic Karenia brevisulcata toxins (KBTs). Karenia mikimotoi did not produce brevetoxin, BSXs or KBTs. The present study confirms the broad threats that blooms of K. brevisulcata pose to marine ecosystems and aquaculture, and the hazards of K. brevis to finfish and K. mikimotoi to abalone respectively.

Population and behavioural responses of native prey to alien predation - Eszter Krasznai Kovacs; Mathew S. Crowther; Jonathan K. Webb; Christopher R. Dickman (Oecologia, 2012)

Total ozone and surface UV trends in the United Kingdom: 1979–2008 - Andrew R. D. Smedley; John S. Rimmer; David Moore; Ralf Toumi; Ann R. Webb (International Journal of Climatology, 2012)
In this study we present the UK's total ozone and UV data records, their measurement and preliminary processing, and discuss the observed trends. Notably, we combine the records from the Camborne and Reading sites to obtain a single ozone data series for southern England—a total duration of 30 years. Two‐section linear trends and cross‐over years are determined for Lerwick and southern England, both annually and seasonally. The observed minimum using this technique in the UK ozone record is found to occur during the year 1993. Significant trends of − 4.8% per decade for southern England and − 5.8% per decade for Lerwick are seen prior to the mid‐1990s; the rate of decrease in the UK being at the upper limit of other European stations. No significant ozone trend is seen for the latter period in either location in contrast with Europe as a whole. We, additionally, compare the satellite‐derived total ozone trends for both locations. The UV record at Reading showed a significant trend from 1993 to 2008 in the daily maximum UV index record (6.6% per decade), despite no significant recovery in the total ozone data series, suggesting a reduction in cloud cover during the midday period. Filtering data to remove other factors shows the erythemal UV to have an ozone‐dependent trend of − 0.11% per year, but this is not statistically significant. We find no correlation between anomalies in the surface UV and total ozone records suggesting that the majority of the inter‐annual variability is due to changes in cloud cover and other effects. Copyright © 2011 Royal Meteorological Society

Use of talcum powder and endometrial cancer risk - Annette S. Neill; Christina M. Nagle; Amanda B. Spurdle; Penelope M. Webb (Cancer Causes & Control, 2012)

Fine-scale spatial temperature patterns across a UK conurbation - Claire L. Smith; A. Webb; G. J. Levermore; S. J. Lindley; K. Beswick (Climatic Change, 2011)

Genetic risk sum score comprised of common polygenic variation is associated with body mass index - Roseann E. Peterson; Hermine H. Maes; Peter Holmans; Alan R. Sanders; Douglas F. Levinson; Jianxin Shi; Kenneth S. Kendler; Pablo V. Gejman; Bradley T. Webb (Human Genetics, 2011)

Local people value environmental services provided by forested parks - Navjot S. Sodhi; Tien Ming Lee; Cagan H. Sekercioglu; Edward L. Webb; Dewi M. Prawiradilaga; David J. Lohman; Naomi E. Pierce; Arvin C. Diesmos; Madhu Rao; Paul R. Ehrlich (Biodiversity and Conservation, 2010)

Gem-corundum megacrysts from east Australian basalt fields: trace elements, oxygen isotopes and origins∗ - F. L. Sutherland; K. Zaw; S. Meffre; G. Giuliani; A. E. Fallick; I. T. Graham; G. B. Webb (Australian Journal of Earth Sciences, 2009)

Physiological responses to simulated stair climbing in professional firefighters wearing rubber and leather boots - Chun-Jung Huang; Ryan S. Garten; Chip Wade; Heather E. Webb; Edmund O. Acevedo (European Journal of Applied Physiology, 2009)

Patterns and causes of species richness: a general simulation model for macroecology - Nicholas J. Gotelli; Marti J. Anderson; Hector T. Arita; Anne Chao; Robert K. Colwell; Sean R. Connolly; David J. Currie; Robert R. Dunn; Gary R. Graves; Jessica L. Green; John‐Arvid Grytnes; Yi‐Huei Jiang; et al. (Ecology Letters, 2009)
Understanding the causes of spatial variation in species richness is a major research focus of biogeography and macroecology. Gridded environmental data and species richness maps have been used in increasingly sophisticated curve‐fitting analyses, but these methods have not brought us much closer to a mechanistic understanding of the patterns. During the past two decades, macroecologists have successfully addressed technical problems posed by spatial autocorrelation, intercorrelation of predictor variables and non‐linearity. However, curve‐fitting approaches are problematic because most theoretical models in macroecology do not make quantitative predictions, and they do not incorporate interactions among multiple forces. As an alternative, we propose a mechanistic modelling approach. We describe computer simulation models of the stochastic origin, spread, and extinction of species’ geographical ranges in an environmentally heterogeneous, gridded domain and describe progress to date regarding their implementation. The output from such a general simulation model (GSM) would, at a minimum, consist of the simulated distribution of species ranges on a map, yielding the predicted number of species in each grid cell of the domain. In contrast to curve‐fitting analysis, simulation modelling explicitly incorporates the processes believed to be affecting the geographical ranges of species and generates a number of quantitative predictions that can be compared to empirical patterns. We describe three of the ‘control knobs’ for a GSM that specify simple rules for dispersal, evolutionary origins and environmental gradients. Binary combinations of different knob settings correspond to eight distinct simulation models, five of which are already represented in the literature of macroecology. The output from such a GSM will include the predicted species richness per grid cell, the range size frequency distribution, the simulated phylogeny and simulated geographical ranges of the component species, all of which can be compared to empirical patterns. Challenges to the development of the GSM include the measurement of goodness of fit (GOF) between observed data and model predictions, as well as the estimation, optimization and interpretation of the model parameters. The simulation approach offers new insights into the origin and maintenance of species richness patterns, and may provide a common framework for investigating the effects of contemporary climate, evolutionary history and geometric constraints on global biodiversity gradients. With further development, the GSM has the potential to provide a conceptual bridge between macroecology and historical biogeography.

Pockmarks in the inner Oslofjord, Norway - Karen E. Webb; Øyvind Hammer; Aivo Lepland; John S. Gray (Geo-Marine Letters, 2009)

A Neisseria meningitidis NMB1966 mutant is impaired for invasion of respiratory epithelial cells, survival in human blood and for virulence in vivo - Ming-Shi Li; Noel Y. S. Chow; Sunita Sinha; Denise Halliwell; Michelle Finney; Andrew R. Gorringe; Mark W. Watson; J. Simon Kroll; Paul R. Langford; Steven A. R. Webb (Medical Microbiology and Immunology, 2009)

Muscle fiber type characteristics in females with chronic obstructive pulmonary disease. A preliminary study - Howard J. Green; M. E. Burnett; C. D’Arsigny; S. Iqbal; J. Ouyang; K. A. Webb; D. E. O’Donnell (Journal of Molecular Histology, 2009)

Emerging patterns in the comparative analysis of phylogenetic community structure - S. M. VAMOSI; S. B. HEARD; J. C. VAMOSI; C. O. WEBB (Molecular Ecology, 2009)
The analysis of the phylogenetic structure of communities can help reveal contemporary ecological interactions, as well as link community ecology with biogeography and the study of character evolution. The number of studies employing this broad approach has increased to the point where comparison of their results can now be used to highlight successes and deficiencies in the approach, and to detect emerging patterns in community organization. We review studies of the phylogenetic structure of communities of different major taxa and trophic levels, across different spatial and phylogenetic scales, and using different metrics and null models. Twenty‐three of 39 studies (59%) find evidence for phylogenetic clustering in contemporary communities, but terrestrial and/or plant systems are heavily over‐represented among published studies. Experimental investigations, although uncommon at present, hold promise for unravelling mechanisms underlying the phylogenetic community structure patterns observed in community surveys. We discuss the relationship between metrics of phylogenetic clustering and tree balance and explore the various emerging biases in taxonomy and pitfalls of scale. Finally, we look beyond one‐dimensional metrics of phylogenetic structure towards multivariate descriptors that better capture the variety of ecological behaviours likely to be exhibited in communities of species with hundreds of millions of years of independent evolution.

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Effects on kidney disease, fertility and development in mice inheriting a protein-truncating Denys-Drash syndrome allele (Wt1 tmT396) - Charles E. Patek; David G. Brownstein; Stewart Fleming; Caroline Wroe; Lorraine Rose; Anna Webb; Rachel L. Berry; Paul S. Devenney; Marion Walker; Oliver D. K. Maddocks; Nicola J. Lawrence; David J. Harrison; et al. (Transgenic Research, 2008)

EhaA is a novel autotransporter protein of enterohemorrhagic Escherichia coli O157:H7 that contributes to adhesion and biofilm formation - Timothy J. Wells; Orla Sherlock; Lucy Rivas; Arvind Mahajan; Scott A. Beatson; Mia Torpdahl; Richard I. Webb; Luke P. Allsopp; Kari S. Gobius; David L. Gally; Mark A. Schembri (Environmental Microbiology, 2008)
Summary Autotransporter (AT) proteins have been identified in many Gram‐negative pathogens and are unique in that their primary sequence is sufficient to direct their transport across the bacterial membrane system. Where characterized they are uniformly associated with virulence. Using conserved AT motifs as a search tool, four putative AT proteins were identified in the Enterohemorrhagic Escherichia coli O157:H7 EDL933 genome. The genes encoding these proteins (z0402/ ehaA , z0469/ ehaB , z3487/ ehaC and z3948/ ehaD ) were PCR amplified, cloned and expressed in an E. coli K‐12 MG1655 flu background. Preliminary characterization revealed that ehaA , ehaB and ehaD encode proteins associated with increased biofilm formation. One of these genes ( ehaA ) resides on a genomic island in E. coli O157:H7 strains EDL933 and Sakai. Over‐expression of EhaA in E. coli K‐12 demonstrated it is located at the cell surface and resulted in the formation of large cell aggregates, promoted significant biofilm formation and mediated adhesion to primary epithelial cells of the bovine terminal rectum. The expression of ehaA was demonstrated in E. coli EDL933 by RT‐PCR. An EhaA‐specific antibody revealed the EhaA protein was expressed in 24/50 generic Shiga toxin‐producing E. coli (STEC) strains of various serotypes including O157:H7. However, the deletion of ehaA from E. coli EDL933 and a STEC strain from serotype O111:H – did not affect biofilm growth. Our results suggest that EhaA may contribute to adhesion, colonization and biofilm formation by E. coli O157:H7 and possibly other STEC serotypes.

Hawksbill sea turtles: can phylogenetics inform harvesting? - MATTHEW H. GODFREY; GRAHAME J. W. WEBB; S. CHARLIE MANOLIS; N. MROSOVSKY (Molecular Ecology, 2007)

In Vitro Characterization of a Compliant Biodegradable Scaffold with a Novel Bioreactor System - Antonio R. Webb; Bryan D. Macrie; Ananda S. Ray; Jack E. Russo; Andrew M. Siegel; Matthew R. Glucksberg; Guillermo A. Ameer (Annals of Biomedical Engineering, 2007)

Decadal- to interannual-scale source water variations in the Caribbean Sea recorded by Puerto Rican coral radiocarbon - K. Halimeda Kilbourne; Terrence M. Quinn; Thomas P. Guilderson; Robert S. Webb; Frederick W. Taylor (Climate Dynamics, 2007)

Comparison of genetic diversity at microsatellite loci in near‐extinct and non‐endangered species of Mexican goodeine fishes and prediction of cross‐amplification within the family - R. M. Hamill; S. A. Webb; C. Macías Garcia; J. A. Graves; A. E. Magurran; M. G. Ritchie (Journal of Fish Biology, 2007)
The cross‐utility of 12 microsatellite loci (including nine newly developed loci) amongst the viviparous subfamily, the Mexican Goodeinae, was assessed, examining both the probability of amplification and the potential incidence of null alleles from tests of F IS . Genetic diversity was relatively high in comparison to other freshwater species. Amplification success was not correlated with genetic distance between microsatellite source and target species, but taxa that were more distantly related were less likely to be cross‐polymorphic for microsatellite loci. On average, species that were cross‐polymorphic were separated by a genetic distance of 15% at the cytochrome oxidase I locus, while those that were monomorphic were separated by 19%. There was no evidence that null alleles become more frequent at greater source‐target genetic distance.

Biomarkers for NeuroAIDS: The Widening Scope of Metabolomics - Gurudutt Pendyala; Elizabeth J. Want; William Webb; Gary Siuzdak; Howard S. Fox (Journal of Neuroimmune Pharmacology, 2007)

Importance of the mixed-phase cloud distribution in the control climate for assessing the response of clouds to carbon dioxide increase: a multi-model study - Yoko Tsushima; S. Emori; T. Ogura; M. Kimoto; M. J. Webb; K. D. Williams; M. A. Ringer; B. J. Soden; B. Li; N. Andronova (Climate Dynamics, 2006)

On the contribution of local feedback mechanisms to the range of climate sensitivity in two GCM ensembles - M. J. Webb; C. A. Senior; D. M. H. Sexton; W. J. Ingram; K. D. Williams; M. A. Ringer; B. J. McAvaney; R. Colman; B. J. Soden; R. Gudgel; T. Knutson; S. Emori; et al. (Climate Dynamics, 2006)

Quantifying Abrasion of Stable Substrata in Streams: A New Disturbance Index for Epilithic Biota - J. Angus Webb; Barbara J. Downes; P. S. Lake; Alena Glaister (Hydrobiologia, 2006)

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River - M. A. H. Webb; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck; M. Plumlee; C. Wong; D. T. Gundersen (Archives of Environmental Contamination and Toxicology, 2006)

Evaluation of a component of the cloud response to climate change in an intercomparison of climate models - K. D. Williams; M. A. Ringer; C. A. Senior; M. J. Webb; B. J. McAvaney; N. Andronova; S. Bony; J. -L. Dufresne; S. Emori; R. Gudgel; T. Knutson; B. Li; et al. (Climate Dynamics, 2006)

Antibody-based therapeutics: Focus on prostate cancer - Jeffrey S. Ross; Karen E. Gray; Iain J. Webb; Gary S. Gray; Mark Rolfe; David P. Schenkein; David M. Nanus; Mathew I. Millowsky; Neil H. Bander (Cancer and Metastasis Reviews, 2005)

Dominantly inherited cutaneous small-vessel lymphocytic vasculitis maps to chromosome 6q26–q27 - Gabrielle S. Sellick; Richard J. Coleman; Emily L. Webb; Jade Chow; Steven Bevan; Jane L. Rosbotham; Richard S. Houlston (Human Genetics, 2005)

Interaction of metastasis-inducing S100A4 protein in vivo by fluorescence lifetime imaging microscopy - Shu Zhang; Guozheng Wang; David G. Fernig; Philip S. Rudland; Stephen E. D. Webb; Roger Barraclough; Marisa Martin-Fernandez (European Biophysics Journal, 2005)

Carbonate alteration of the Upper Mount McRae Shale beneath the martite-microplaty hematite ore deposit at Mount Whaleback, Western Australia - Adam D. Webb; Gerald R. Dickens; Nicholas H. S. Oliver (Mineralium Deposita, 2004)

Emissions of ammonia and nitrous oxide following incorporation into the soil of farmyard manures stored at different densities - J. Webb; D. Chadwick; S. Ellis (Nutrient Cycling in Agroecosystems, 2004)

Movements and burrowing activity in the Antarctic bivalve molluscs Laternula elliptica and Yoldia eightsi - Lloyd S. Peck; Alan D. Ansell; Karen E. Webb; Leanne Hepburn; Michael Burrows (Polar Biology, 2004)

Mixing of Stably Stratified Gases in Subsurface Reservoirs: A Comparison of Diffusion Models - C. M. Oldenburg; S. W. Webb; K. Pruess; G. J. Moridis (Transport in Porous Media, 2004)

Measurement of N fluxes and soil N in two arable soils in the UK - J. Webb; S. Ellis; R. Harrison; R. Thorman (Plant and Soil, 2004)

Response of Nebraska Sand Hills Natural Vegetation to Drought, Fire, Grazing, and Plant Functional Type Shifts as Simulated by the Century Model - Jennifer M. Mangan; Jonathan T. Overpeck; Robert S. Webb; Carol Wessman; Alexander F. H. Goetz (Climatic Change, 2004)

A floristic analysis of the lowland dipterocarp forests of Borneo - J. W. F. Slik; A. D. Poulsen; P. S. Ashton; C. H. Cannon; K. A. O. Eichhorn; K. Kartawinata; I. Lanniari; H. Nagamasu; M. Nakagawa; M. G. L. Van Nieuwstadt; J. Payne; Purwaningsih; et al. (Journal of Biogeography, 2003)
Aim To (1) identify floristic regions in the lowland (below 500 m a.s.l.) tropical dipterocarp rain forest of Borneo based on tree genera, (2) determine the characteristic taxa of these regions, (3) study tree diversity patterns within Borneo, and (4) relate the floristic and diversity patterns to abiotic factors such as mean annual rainfall and geographical distance between plots. Location Lowland tropical dipterocarp rain forest of Borneo. Methods We used tree (diameter at breast height ≥ 9.8 cm) inventory data from 28 lowland dipterocarp rain forest locations throughout Borneo. From each location six samples of 640 individuals were drawn randomly. With these data we calculated a Sørensen and Steinhaus similarity matrix for the locations. These matrices were then used in an UPGMA clustering algorithm to determine the floristic relations between the locations (dendrogram). Principal coordinate analysis was used to ordinate the locations. Characteristic taxa for the identified floristic clusters were determined with the use of the INDVAL method of Dufrene & Legendre (1997) . Finally, Mantel analysis was applied to determine the influence of mean annual rainfall and geographical distance between plots on floristic composition. Results A total of 77 families and 363 genera were included in the analysis. On average a random sample of 640 trees from a lowland dipterocarp forest in Borneo contains 41.6 ± 3.8 families and 103.0 ± 12.7 genera. Diversity varied strongly on local scales. On a regional scale, diversity was found to be highest in south‐east Borneo and central Sarawak. The most common families were Dipterocarpaceae (21.9% of trees) and Euphorbiaceae (12.2% of trees). The most common genera were Shorea (12.3% of trees) and Syzygium (5.0% of trees). The 28 locations were clustered in geographically distinct floristic regions. This was related to the fact that floristic similarity depended strongly on the geographical distance between plots and similarity in mean annual rainfall. Conclusions We identified five main floristic regions within the lowland dipterocarp rain forests of Borneo, each of which had its own set of characteristic genera. Mean annual rainfall is an important factor in explaining differences in floristic composition between locations. The influence of geographical distance on floristic similarity between locations is probably related to the fact that abiotic factors change with distance between plots. Borneo's central mountain range generally forms an effective dispersal barrier for the lowland tree flora. Diversity patterns in Borneo are influenced by the mid‐domain effect, habitat size and the influence of past climatic changes (ice ages during the Pleistocene).

Synergistic interactions between chemical alarm cues and the presence of conspecific and heterospecific fish shoals - Brian D. Wisenden; Mike S. Pollock; Robyn J. Tremaine; Jeff M. Webb; Monique E. Wismer; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2003)

Aerial dispersal of invertebrates over a high-Arctic glacier foreland: Midtre Lovnbreen, Svalbard - S. J. Coulson; I. D. Hodkinson; N. R. Webb (Polar Biology, 2003)

A high-Arctic population of Pyla fusca (Lepidoptera, Pyralidae) on Svalbard? - S. J. Coulson; I. D. Hodkinson; N. R. Webb; P. Convey (Polar Biology, 2003)

Anelasticity and microcreep in polycrystalline MgO at high temperature: an exploratory study - S. Webb; I. Jackson (Physics and Chemistry of Minerals, 2003)

Genetic evidence for two sibling species within Contracaecum ogmorhini Johnston & Mawson, 1941 (Nematoda: Anisakidae) from otariid seals of boreal and austral regions - S. Mattiucci; R. Cianchi; G. Nascetti; L. Paggi; N. Sardella; J. Timi; S.C. Webb; R. Bastida; D. Rodríguez; L. Bullini (Systematic Parasitology, 2003)

Wavelength-Resolved 3-Dimensional Fluorescence Lifetime Imaging - S. E. D. Webb; S. Lévêque-Fort; D. S. Elson; J. Siegel; T. Watson; M. J. Lever; M. Booth; R. Juskaitis; M. A. A. Neil; L. O. Sucharov; T. Wilson; P. M. W. French (Journal of Fluorescence, 2002)

In Situ Detection of the Pathogen Indicator E. coli Using Active Laser-Induced Fluorescence Imaging and Defined Substrate Conversion - J. Anderson; S. Webb; R. Fischer; C. Smith; J. Dennis; J. Di Benedetto (Journal of Fluorescence, 2002)

Evaluating the coastal environment for marine birds - S. Wanless; P. J. Bacon; M. P. Harris; A. D. Webb (Journal of Coastal Conservation, 2002)

Combining ERBE and ISCCP data to assess clouds in the Hadley Centre, ECMWF and LMD atmospheric climate models - M. Webb; C. Senior; S. Bony; J.-J. Morcrette (Climate Dynamics, 2001)

Intercomparison of national & IPCC methods for estimating N loss from agricultural land - M. Silgram; R. Waring; S. Anthony; J. Webb (Nutrient Cycling in Agroecosystems, 2001)

Emission of ammonia (NH3), nitrous oxide (N2O) and methane (CH4) from a dairy hardstanding in the UK - S. Ellis; J. Webb; T. Misselbrook; D. Chadwick (Nutrient Cycling in Agroecosystems, 2001)

Amey: A multipurpose, russet-skinned potato cultivar for the Eastern United States - K. G. Haynes; G. A. Porter; B. J. Christ; R. W. Goth; K. O. DeLong; D. E. Halseth; J. B. Sieczka; M. R. Henninger; S. B. Sterrett; G. C. Yencho; R. E. Webb (American Journal of Potato Research, 2001)

Spawning success in Atlantic salmon ( Salmo salar L.): a long‐term DNA profiling‐based study conducted in a natural stream - J. B. Taggart; I. S. McLaren; D. W. Hay; J. H. Webb; A. F. Youngson (Molecular Ecology, 2001)
Spawning success of Atlantic salmon ( Salmo salar L.) was investigated, under near‐natural conditions, in the Girnock Burn, an 8‐km long tributary of the River Dee in Scotland. Employing minisatellite‐based DNA profiling, mating outcomes were resolved over three spawning seasons by assigning parentage to progeny samples removed from spawning nests (‘redds’). While individual spawning patterns differed markedly, consistent trends were present over the 3 years studied. Multiple spawning was found to be prevalent. More than 50% of anadromous spawners of both sexes contributed to more than one redd. Up to six redds for a single female and seven for a single male were detected. Both sexes ranged extensively. Distance between redds involving the same parent varied from a few metres to > 5 km. Distances > 1 km were common. Both males and females ranged to a similar extent. Range limit was not correlated to fish size. Pairs were not monogamous, both males and females mating with different partners at different sites. Size assortative mating was apparent among 1991 spawners but was not detected for 1992 or 1995. Redd superimposition was found to be common (17–22% of redds over the 3 years), although it was not correlated to the number of anadromous spawners present. High levels of nonanadromous mature parr mating success (40–50% of total progeny sampled) were recorded, and these likely contribute greatly to the effective population size. The relevance of these findings at the individual and population level is discussed, with particular reference to management implications.

The effects of copper on the microbial community of a coral reef sponge - Nicole S. Webster; Richard I. Webb; Michael J. Ridd; Russell T. Hill; Andrew P. Negri (Environmental Microbiology, 2001)
Marine sponges often harbour communities of symbiotic microorganisms that fulfil necessary functions for the well‐being of their hosts. Microbial communities associated with the sponge Rhopaloeides odorabile were used as bioindicators for sublethal cupric ion (Cu 2+ ) stress. A combined strategy incorporating molecular, cultivation and electron microscopy techniques was adopted to monitor changes in microbial diversity. The total density of sponge‐associated bacteria and counts of the predominant cultivated symbiont (α‐proteobacterium strain NW001) were significantly reduced in response to Cu 2+ concentrations of 1.7 µg l −1 and above after 14 days of exposure. The number of operational taxonomic units (OTUs) detected by restriction fragment length polymorphism (RFLP) decreased by 64% in sponges exposed to 223 µg l −1 Cu 2+ for 48 h and by 46% in sponges exposed to 19.4 µg l −1 Cu 2+ for 14 days. Electron microscopy was used to identify 17 predominant bacterial morphotypes, composing 47% of the total observed cells in control sponges. A reduction in the proportion of these morphotypes to 25% of observed cells was evident in sponges exposed to a Cu 2+ concentration of 19.4 µg l −1 . Although the abundance of most morphotypes decreased under Cu 2+ stress, three morphotypes were not reduced in numbers and a single morphotype actually increased in abundance. Bacterial numbers, as detected using fluorescence in situ hybridization (FISH), decreased significantly after 48 h exposure to 19.4 µg l −1 Cu 2+ . Archaea, which are normally prolific in R. odorabile , were not detected after exposure to a Cu 2+ concentration of 19.4 µg l −1 for 14 days, indicating that many of the microorganisms associated with R. odorabile are sensitive to free copper. Sponges exposed to a Cu 2+ concentration of 223 µg l −1 became highly necrosed after 48 h and accumulated 142 ± 18 mg kg −1 copper, whereas sponges exposed to 19.4 µg l −1 Cu 2+ accumulated 306 ± 15 mg kg −1 copper after 14 days without apoptosis or mortality. Not only do sponges have potential for monitoring elevated concentrations of heavy metals but also examining changes in their microbial symbionts is a novel and sensitive bioindicator for the assessment of pollution on important microbial communities.

Last glacial maximum biomes reconstructed from pollen and plant macrofossil data from northern Eurasia - P. E. Tarasov; V. S. Volkova; T. Webb; J. Guiot; A. A. Andreev; L. G. Bezusko; T. V. Bezusko; G. V. Bykova; N. I. Dorofeyuk; E. V. Kvavadze; I. M. Osipova; N. K. Panova; et al. (Journal of Biogeography, 2000)
Pollen and plant macrofossil data from northern Eurasia were used to reconstruct the vegetation of the last glacial maximum (LGM: 18,000 ± 2000 14 C yr bp ) using an objective quantitative method for interpreting pollen data in terms of the biomes they represent ( Prentice et al. , 1996 ). The results confirm previous qualitative vegetation reconstructions at the LGM but provide a more comprehensive analysis of the data. Tundra dominated a large area of northern Eurasia (north of 57°N) to the west, south and east of the Scandinavian ice sheet at the LGM. Steppe‐like vegetation was reconstructed in the latitudinal band from western Ukraine, where temperate deciduous forests grow today, to western Siberia, where taiga and cold deciduous forests grow today. The reconstruction shows that steppe graded into tundra in Siberia, which is not the case today. Taiga grew on the northern coast of the Sea of Azov, about 1500 km south of its present limit in European Russia. In contrast, taiga was reconstructed only slightly south of its southern limit today in south‐western Siberia. Broadleaved trees were confined to small refuges, e.g. on the eastern coast of the Black Sea, where cool mixed forest was reconstructed from the LGM data. Cool conifer forests in western Georgia were reconstructed as growing more than 1000 m lower than they grow today. The few scattered sites with LGM data from the Tien‐Shan Mountains and from northern Mongolia yielded biome reconstructions of steppe and taiga, which are the biomes growing there today.

A modified Bläzka–type respirometer for the study of swimming metabolism in fishes having deep, laterally compressed bodies or unusual locomotor modes - J. R. Hove; M. S Gordon; P. W. Webb; D. Weihs (Journal of Fish Biology, 2000)
A low volume (8·4 l), rectangular (cross–section) respirometer modified from a Bläzka–type coaxial circuit, which provides rectilinear flow at speeds up to 0·36 m s –1 , is described.

Isolation and characterization of a Clostridium sp. with cinnamoyl esterase activity and unusual cell envelope ultrastructure - C. S. McSweeney; Amanda Dulieu; Richard I. Webb; Therese Del Dot; Linda L. Blackall (Archives of Microbiology, 1999)

LAMSA laboratory animal management system - M.A. Mckie; S. Webb (Mammalian Genome, 1999)

Hydrology, water availability and tundra ecosystem function in a changing climate: the need for a closer integration of ideas? - I. D. Hodkinson; N. R. Webb; J. S. Bale; W. Block (Global Change Biology, 1999)
Hydrologists and ecologists studying tundra ecosystems have worked largely independently, with little cross‐fertilization between disciplines. Their disciplines are, however, inextricably linked by a need to understand the dynamics and significance of the common substance water, in its liquid, solid and gaseous state within tundra environments. The impacts of predicted long‐term changes in climate have particularly important consequences for the functioning of tundra systems and there is a pressing need to initiate studies that integrate hydrological and ecological methodologies and concepts. Our paper attempts to summarize existing information on the role of water within tundra ecosystems, to emphasize the fundamental links between the biotic and the physico/chemical environments and to suggest how a closer integration of ideas might be achieved. Given the breadth of the subject matter the paper is intended to be illustrative rather than comprehensive. The paper examines the physical impacts of water in its various states on the tundra environment, emphasizing in particular the causes of spatial variation in water availability to living organisms. The significance of water is discussed for a range of organism groups, including plants, invertebrates and microorganisms and its pivotal role in ecosystem function and disturbance stressed. The need to develop integrated hydological/ecological models for tundra systems on different spatial scales is emphasized.

Ultrastructural visualization of protein-4 binding insulin-like growth factors in cow ovarian follicles - A. L. Glazyrin; D. G. Armstrong; K. G. Guttieras; T. A. Bramley; R. Webb; S. I. Kolesnikov (Bulletin of Experimental Biology and Medicine, 1998)

Present‐day and mid‐Holocene biomes reconstructed from pollen and plant macrofossil data from the former Soviet Union and Mongolia - Pavel E. Tarasov; Thompson Webb III; Andrei A. Andreev; Natalya B. Afanas’eva; Natalya A. Berezina; Ludmila G. Bezusko; Tatyana A. Blyakharchuk; Natalia S. Bolikhovskaya; Rachid Cheddadi; Margarita M. Chernavskaya; Galina M. Chernova; Nadezhda I. Dorofeyuk; et al. (Journal of Biogeography, 1998)
Fossil pollen data supplemented by tree macrofossil records were used to reconstruct the vegetation of the Former Soviet Union and Mongolia at 6000 years. Pollen spectra were assigned to biomes using the plant‐functional‐type method developed by Prentice et al . (1996). Surface pollen data and a modern vegetation map provided a test of the method. This is the first time such a broad‐scale vegetation reconstruction for the greater part of northern Eurasia has been attempted with objective techniques. The new results confirm previous regional palaeoenvironmental studies of the mid‐Holocene while providing a comprehensive synopsis and firmer conclusions. West of the Ural Mountains temperate deciduous forest extended both northward and southward from its modern range. The northern limits of cool mixed and cool conifer forests were also further north than present. Taiga was reduced in European Russia, but was extended into Yakutia where now there is cold deciduous forest. The northern limit of taiga was extended (as shown by increased Picea pollen percentages, and by tree macrofossil records north of the present‐day forest limit) but tundra was still present in north‐eastern Siberia. The boundary between forest and steppe in the continental interior did not shift substantially, and dry conditions similar to present existed in western Mongolia and north of the Aral Sea.

Phylogenetic relationships of species of Gingidia and related genera (Apiaceae, subfamily Apioideae) - A. D. Mitchell; C. J. Webb; S. J. Wagstaff (New Zealand Journal of Botany, 1998)
Five genera of Australasian apioid Apiaceae (Gingidia, Scandia, Lignocarpa, Anisotome, and Aciphylla) have a complex taxo‐nomic history with the circumscription of, and inferred relationships among, the currently accepted genera based on only morphological characters. This molecular and phylogenetic study focuses on the relationships among the taxa currently included within Gingidia using the other genera as outgroups. Phylogenetic analyses of nuclear ribosomal DNA internal transcribed spacer region sequences for 17 species from these genera, and comparison with Smyrnium to root the trees, indicate that Gingidia is polyphyletic as currently circumscribed, the species belonging in two distinct monophyletic groups. However, morphological characters do not support these two groups, making taxonomic interpretation difficult. The monophyletic G. montana group includes the ditypic endemic genera Scandia and Lignocarpa, suggesting that they should not be maintained. The second monophyletic group includes G. decipiens and G. flabellata with species of Anisotome. Although our sampling of Anisotome and Aciphylla is limited, nothing in the analysis of the molecular data is inconsistent with earlier suggestions, based on morphological data, that Gingidia, Scandia, Lignocarpa, Anisotome, and Aciphylla form a monophyletic group.

Forest Integrity at Anthropogenic Edges: Air Pollution Disrupts Bioindicators - Marian G. Glenn; Sara L. Webb; Mariette S. Cole (Environmental Monitoring and Assessment, 1998)

Physiological and morphological variation in Metrosideros polymorpha , a dominant Hawaiian tree species, along an altitudinal gradient: the role of phenotypic plasticity - S. Cordell; G. Goldstein; D. Mueller-Dombois; D. Webb; P. M. Vitousek (Oecologia, 1998)

Srbl maps to mouse Chromosome 5 in a region harboring putative QTLs for plasma lipoprotein levels - Carrie L. Welch; Yu-Rong Xia; Ling-Jie Gu; Dietrich Machleder; Margarete Mehrabian; Ping-Zi Wen; Nancy Webb; Willem J. S. de Villiers; Deneys van der Westhuyzen; Aidons J. Lusis (Mammalian Genome, 1997)

Biosedimentology of Microbial Buildups IGCP Project No. 380 Proceedings of 2nd Meeting, Göttingen/Germany 1996 - Fritz Neuweiler; Joachim Reitner; Claude Monty; Mark Feldmann; Stan Awramik; Pierre-André Bourque; Simonetta Cirilli; Pascale Gautret; Jean Marcoux; Jean Claude Plaziat; Christian Défarge; Jean Trichet; et al. (Facies, 1997)

Physical properties of the 1980 Mount St. Helens cryptodome magma - M. Alidibirov; D. B. Dingwell; R. J. Stevenson; K.-U. Hess; S. L. Webb; J. Zinke (Bulletin of Volcanology, 1997)

Evidence of acoustic startle hyperreflexia in recently detoxified early onset male alcoholics: modulation by yohimbine and m -Chlorophenylpiperazine (mCPP) - John H. Krystal; Elizabeth Webb; Christian Grillon; N. Cooney; Lisa Casal; C. A. Morgan III.; Steven M. Southwick; Michael Davis; Dennis S. Charney (Psychopharmacology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Evaluation of potato cultivars, clones and a true seed population for resistance toRhizoctonia solani - Simeon S. Leach; Raymon E. Webb (American Journal of Potato Research, 1993)

Coastal Chip: A chipping potato variety resistant to heat stress - K. G. Haynes; R. W. Goth; S. B. Sterrett; B. J. Christ; D. E. Halseth; G. A. Porter; M. R. Henninger; D. R. Wilson; R. E. Webb; D. F. Hammond; R. Moore; F. L. Haynes; et al. (American Journal of Potato Research, 1992)

A simple action treshold for timing applications of a granulosis virus to controlPieris rapae [Lep.: Pieridae] - S. E. Webb; A. M. Shelton (BioControl, 1991)

Coastal Russet: a mid-season Russet-skinned potato cultivar - J. B. Sieczka; R. E. Webb; D. R. Wilson; D. E. Halseth; S. B. Sterrett; M. R. Henninger; G. A. Porter; J. R. Shumaker; R. Moore (American Journal of Potato Research, 1988)

Coastal Russet: A mid-season Russet-skinned potato cultivar - J. B. Sieczka; R. E. Webb; D. R. Wilson; D. E. Halseth; S. B. Sterrett; M. R. Henninger; G. A. Porter; J. R. Shumaker; R. Moore (American Journal of Potato Research, 1988)

Canopy photosynthesis, stomatal conductance and yield ofSolanum tuberosum grown in a warm climate - Ajmer S. Bhagsari; Raymon E. Webb; Sharad C. Phatak; Casimir A. Jaworski (American Journal of Potato Research, 1988)

Laal-e-faisal: A new red skin potato variety adapted to Pakistan - A. H. Chaudhry; Kh. Imdad Hussain; A. H. Tariq; S. M. A. Shah; R. E. Webb (American Journal of Potato Research, 1987)

The chronic toxicity of equine cadmium metallothionein in the rat - Daphne Holt; S. Sparrow; M. Webb (Archives of Toxicology, 1985)

Genetic and environmental control of potato glycoalkaloids - S. L. Sinden; L. L. Sanford; R. E. Webb (American Journal of Potato Research, 1984)

The nature of cadmium binding in commercial Eastern Oysters (Crassostrea virginica) - T. C. Siewicki; J. S. Sydlowski; E. S. Webb (Archives of Environmental Contamination and Toxicology, 1983)

Relative resistance of potato cultivars to bacterial wilt - C. A. Jaworski; R. E. Webb; R. W. Goth; S. C. Phatak (American Journal of Potato Research, 1980)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)

Effect of variety and location on the glycoalkaloid content of potatoes - S. L. Sinden; R. E. Webb (American Journal of Potato Research, 1972)

Tests with milk and rice polish to prevent infection of Irish potato with virus Y transmitted by aphids - W. A. Shands; R. E. Webb; E. S. Schultz (American Journal of Potato Research, 1962)

Resistance of solanum species to potato viruses A, X, and Y - R. E. Webb; E. S. Schultz (American Journal of Potato Research, 1961)

The importance of the spring migrants of the buckthorn aphid in the spread of potato virus Y - W. A. Shands; R. E. Webb; E. S. Schultz (American Journal of Potato Research, 1961)

The evaluation of potato seedling varieties for field immunity from potato virus A - R. E. Webb; E. S. Schultz (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

Late blight investigations - M. E. Gallegly; Reiner Bonde; C. J. Eide; J. L. Howatt; J. S. Niederhauser; L. C. Peterson; W. R. Mills; R. E. Webb (American Journal of Potato Research, 1958)

Influence of daylength and temperature on diagnosis of immunity from virus X in potato - R. E. Webb; E. S. Schultz (American Journal of Potato Research, 1957)

Preliminary studies on corky ringspot of potato - R. E. Webb; E. S. Schultz (American Journal of Potato Research, 1957)

s of papers presented at Annual Meeting - F. Heiligman; J. R. Wagner; WM. G. Hoyman; Jack R. Wallin; D. R. Isleib; N. R. Thompson; Robert H. Johansen; Knutson Kenneth; Carl J. Eide; F. A. Krantz; Florian Lauer; F. I. Lauer; et al. (American Journal of Potato Research, 1957)

Some variations in symptomatology and transmission of leafroll in potato - R. E. Webb; E. S. Schultz; R. V. Akeley (American Journal of Potato Research, 1955)